Method for wrapping absorbent article

By introducing flexible bonding channel areas into absorbent products and utilizing the elasticity and plasticity of the nonwoven layer, the problem of traditional absorbent products being difficult to conform closely in the longitudinal and transverse directions is solved, achieving better body fit and leakage prevention.

CN119278013APending Publication Date: 2025-01-07PROCTER & GAMBLE CO
View PDF 60 Cites 0 Cited by

Patent Information

Application Number
CN202380041265.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-01-18
Filing Date
2023-05-17
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Traditional absorbent products are difficult to conform closely to the body in both the longitudinal and lateral directions, leading to an increased risk of leakage, especially near the areas where bodily fluids are expelled.

Method used

The absorbent core structure employs a flexible bonding channel region. By forming a flexible bonding channel region in the absorbent product, the elasticity and plasticity of the upper and lower nonwoven layers allow the absorbent product to flexibly bend in the longitudinal and transverse directions, thereby closely conforming to the body.

Benefits of technology

It achieves flexible conformability of the absorbent material in both longitudinal and transverse directions, reducing the risk of leakage while maintaining the ability to absorb and retain liquid.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119278013A_ABST
    Figure CN119278013A_ABST
Patent Text Reader

Abstract

A disposable absorbent article has a front end region, a rear end region, and an intermediate region disposed between the front end region and the rear end region. The absorbent article comprises a topsheet; a backsheet; an absorbent core structure disposed between the topsheet and the backsheet; and a flexural bonded channel region formed in at least the intermediate region. The absorbent core structure includes an upper non-woven layer having polymeric fibers; a lower nonwoven layer having polymer fibers; and an inner core layer disposed between the upper nonwoven layer and the lower nonwoven layer. The flexural bonded channel region has a dry channel depth of at least 1.0 mm and a channel width of from about 1.0 mm to about 3.0 mm. The flexural bonded channel region has a CD bending index of from about 1.1 to about 3.0, and a dry MD bending resistance of less than about 0.04 N / mm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to absorbent articles having flex bond channel areas. More particularly, the present invention relates to absorbent articles having flex bond channel areas that are still flexible and conform closely to the body. Background Art

[0002] Absorbent articles such as diapers, training pants, feminine pads, adult incontinence pads, etc. are widely used by consumers. Generally speaking, absorbent articles such as these include a top sheet and a back sheet, wherein an absorbent core structure is disposed between the top sheet and the back sheet. These absorbent articles are designed to absorb and retain liquids and other excreta from the human body to prevent soiling of the body and clothing.

[0003] In order to effectively absorb body fluids without leakage, absorbent articles should be closely conformed to the body of the wearer so that the absorbent article can capture body fluids at the expected position of the absorbent article (e.g., the center of the absorbent core structure). Historically, for menstrual applications, channels produced by embossing have been used to produce bending lines in thicker and / or harder products to provide specific pad shapes in use and help improve the fit to the body. In traditional cellulose-based absorbent core structures, channels are formed by applying high compression forces to densify the cellulose to the extent that the cellulose is irreversibly compressed. Although such channels can provide preferential bending positions in absorbent articles, the high compression forces (i.e., densification) required to produce channels (and keep the channels in place) produce stiffness that can hinder the ability of absorbent articles to conform to the wearer's body in the longitudinal and transverse directions. Therefore, it is not believed that these products conform or fit the wearer's body as closely as possible, especially at the portion adjacent to the body fluid discharge portion in use, and therefore leakage is possible. In order to effectively conform to the body, it is expected that absorbent articles can be bent at preferential positions in the longitudinal and transverse directions.

[0004] There is a need for an absorbent article that includes channels but can still conform to the body and is flexible in both the longitudinal and lateral directions. Summary of the invention

[0005] The present disclosure solves the problem of absorbent articles having rigid and non-conformable channels by providing an absorbent core structure that can sandwich a liquid absorbent material between two nonwoven layers that are plastically deformable to form a flexure bonded channel region without requiring high densification of the absorbent core structure and / or the inner core layer. As described herein, the flexure bonded channel region can be flexible in both the longitudinal and transverse directions, thereby allowing the absorbent article to conform closely to the body.

[0006] The absorbent article comprises: a front end region, a rear end region, and an intermediate region arranged between the front end region and the rear end region; a top sheet; a bottom sheet; an absorbent core structure, which is arranged between the top sheet and the bottom sheet, wherein the absorbent core structure comprises: (a) an upper nonwoven layer, which comprises polymer fibers; (b) a lower nonwoven layer, which comprises polymer fibers; and (c) an inner core layer, which is arranged between the upper nonwoven layer and the lower nonwoven layer, wherein the inner core layer comprises cellulose fibers and superabsorbent particles; and a flexural bond channel region, which is formed in at least the intermediate region, wherein the flexural bond channel region has a dry channel depth of at least 1.0 mm and a width of about 1.0 mm to about 3.0 mm; and wherein the flexural bond channel region has a CD bending resistance index of about 1.1 to about 3.0, and a dry MD bending resistance of less than about 0.04 N / mm, as measured according to the flexural bond channel MD bending resistance method.

[0007] A disposable absorbent article comprises a top sheet; a back sheet; an absorbent core structure disposed between the top sheet and the back sheet; wherein the top sheet forms the wearer-facing surface of the absorbent article, and the back sheet forms the outward-facing surface of the absorbent article; wherein the absorbent core structure comprises: (a) an upper nonwoven layer, the upper nonwoven layer comprising polymer fibers; (b) a lower nonwoven layer, the lower nonwoven layer comprising polymer fibers; and (c) an inner core layer, the inner core layer disposed between the upper nonwoven layer and the lower nonwoven layer; wherein the inner core layer comprises cellulosic fibers and superabsorbent particles; wherein the inner core layer comprises about 125 gsm to about 400 gsm of cellulosic fibers; wherein the wearer-facing surface of the absorbent article comprises a flexural bond channel area, the flexural bond channel area having a dry MD flexural resistance of less than about 0.04 N / mm as measured according to the Flexural Bond Channel MD Flexural Resistance Method and a density of about 0.05 g / cm3 to about 0.3 g / cm3.

[0008] A disposable absorbent article comprises a top sheet; a back sheet; an absorbent core structure disposed between the top sheet and the back sheet, wherein the absorbent core structure comprises an upper nonwoven layer comprising polymer fibers and an inner core layer comprising about 125 gsm to about 400 gsm of cellulosic fibers; wherein the inner core layer has a wearer-facing surface and an outward-facing surface, and the upper nonwoven layer is in direct contact with the wearer-facing surface of the inner core layer; and a flexural bond channel region comprising one or more flexural bond embossments having an embossment length of about 1.0 mm to about 4.0 mm; wherein the flexural bond channel region has a channel depth of at least 1.0 mm and a width of about 1.0 mm to about 3.0 mm; wherein the flexural bond channel region has a dry MD flexural resistance of less than about 0.04 N / mm, as measured according to the Flexural Bond Channel MD Flexural Resistance Method. BRIEF DESCRIPTION OF THE DRAWINGS

[0009] Figure 1 is a schematic diagram of an absorbent core structure according to the present disclosure.

[0010] Figure 2A is a schematic diagram of an absorbent article according to the present disclosure.

[0011] Figure 2B is another schematic illustration of an absorbent article according to the present disclosure.

[0012] Figure 3 It is a cross section of the absorbent core structure.

[0013] Figure 4 is a close-up illustration of a structural bonding site in accordance with the present disclosure.

[0014] Figure 5 yes Figure 4 Cross section of a structural bonding site.

[0015] Figure 6 is a cross-section of an absorbent article according to the present disclosure.

[0016] Fig. 7A is a representation of a top view of an absorbent article having a flex bond channel area according to the present disclosure.

[0017] Figure 7B is a top view of another representation of an absorbent article having flex bond channel areas according to the present disclosure.

[0018] Figure 8 is an enlarged top view illustration of a surface of an absorbent article including a flex bond channel area.

[0019] Fig. 9 is a perspective view illustration of a flex bond channel area in an absorbent article according to the present disclosure.

[0020] Fig. 10A and Fig. 10B is along Fig. 7A Partial cross-sectional view of an absorbent article including flex bond channel areas according to various non-limiting configurations of the present disclosure, taken along line 10-10.

[0021] FIG. 11A to FIG. 11C It is a test method arrangement for wet and dry CD ultra-sensitive 3-point bending method.

[0022] Fig.12 , Fig.13A and Fig. 13B It is a test method arrangement for wet and dry bunching compression testing.

[0023] Fig.14A and Fig. 14B is an exemplary graph of gather curves produced by wet and dry gather compression tests. Fig.14A and Fig. 14B The graphs in are shown to illustrate how the calculations in the method may be performed and do not represent the data described herein.

[0024] Fig.15 is an exemplary graph of channel depth and width of flex bond channel area relative to non-channelized area produced by the flex bond channel depth and width method. Fig.15 The graphs in are shown to illustrate how the calculations in the method may be performed and do not represent the data described herein. DETAILED DESCRIPTION

[0025] As used herein, "disposable absorbent article" or "absorbent article" shall be used with reference to articles such as diapers, training pants, diaper pants, refastenable pants, adult incontinence pads, adult incontinence pants, feminine hygiene pads, cleansing pads, and the like, each of which is intended to be discarded after use.

[0026] As used herein, "absorbent core structure" shall be used with reference to an upper nonwoven layer, a lower nonwoven layer, and an inner core layer disposed between the upper nonwoven layer and the lower nonwoven layer.

[0027] As used herein, "hydrophilic" and "hydrophobic" have the meanings generally accepted in the art with respect to the contact angle of water on the surface of a material. Thus, a material having a water contact angle greater than about 90 degrees is considered hydrophobic, and a material having a water contact angle less than about 90 degrees is considered hydrophilic. A hydrophobic composition will increase the contact angle of water on the surface of a material, while a hydrophilic composition will decrease the contact angle of water on the surface of a material. Although described above, reference to relative hydrophobicity or hydrophilicity between a material and a composition, between two materials, and / or between two compositions does not mean that a material or composition is hydrophobic or hydrophilic. For example, a composition may be more hydrophobic than a material. In this case, neither the composition nor the material may be hydrophobic; however, the contact angle exhibited by the composition is greater than the contact angle of the material. As another example, a composition may be more hydrophilic than a material. In this case, neither the composition nor the material may be hydrophilic; however, the contact angle exhibited by the composition may be less than the contact angle exhibited by the material.

[0028] As used herein, "machine direction" refers to the direction in which a web flows through the absorbent article conversion process. For simplicity, the cross-machine direction may be referred to as "MD".

[0029] As used herein, "cross direction" refers to the direction perpendicular to the MD. For simplicity, the cross direction may be referred to as "CD".

[0030] As used herein, "elastic" refers to a material that tends to retain its shape in both dry and wet states and when subjected to a compressive force tends to recover its original pre-compressed shape when such force is removed. In some aspects, the upper and / or lower nonwoven layers described herein may be elastic.

[0031] As used herein, "wearer-facing" (sometimes referred to herein as body-facing) and "outward-facing" (sometimes referred to herein as garment-facing) refer to the relative position of an element or the relative position of a surface of an element or a group of elements, respectively. "Wearer-facing" means that an element or surface is closer to the wearer than some other element or surface during wear. "Outward-facing" means that an element or surface is farther from the wearer than some other element or surface during wear (i.e., the element or surface is near the wearer's clothing, which may be worn over the absorbent article).

[0032] With respect to a first feature of an article and its positioning relative to a second feature or location on the article, "inboard" means that the first feature is closer to the corresponding axis of the article than the second feature or location along the horizontal xy plane that is roughly occupied by the article when laid flat, extended to the full longitudinal dimensions of its component web materials and transverse dimensions to resist any contraction caused by any included pre-strained elastomeric material on the horizontal surface. Laterally inboard means that the first feature is closer to the longitudinal axis, and longitudinally inboard means that the first feature is closer to the transverse axis. Conversely, with respect to a first feature of an article and its positioning relative to a second feature or location on the article, "outboard" means that the first feature is farther from the corresponding axis of the article than the second feature or location.

[0033] It should be understood that each maximum numerical limitation given throughout this specification includes each lower numerical limitation, as if such lower numerical limitations were expressly written herein. Each minimum numerical limitation given throughout this specification will include each higher numerical limitation, as if such higher numerical limitations were expressly written herein. Each numerical range given throughout this specification will include each narrower numerical range falling within such wider numerical range, as if such narrower numerical ranges were all expressly written herein.

[0034] Disposable absorbent article as described herein may include a top sheet, a back sheet and an absorbent core structure arranged between the top sheet and the back sheet. The absorbent core structure may include an upper nonwoven layer and a lower nonwoven layer, wherein the inner core layer is arranged between the upper nonwoven layer and the lower nonwoven layer. The inner core layer may be included in the nonwoven layer by substantially sealing at least the left region and the right region of the upper nonwoven layer and the lower nonwoven layer at the perimeter seal. In some configurations, the upper nonwoven layer and the lower nonwoven layer may be engaged at the perimeter seal extending around the entire periphery of the inner core layer. Absorbent article may also include one or more flexure bonding channel regions, and this flexure bonding channel region includes the flexure bonding embossing at close intervals.

[0035] As used herein, "flex bond channel area" refers to a generally elongated depression formed in at least a portion of an absorbent article that extends partially or completely through the z-direction thickness of the absorbent article. The flex bond channel area can reduce the thickness of the absorbent article in the z-direction and can act as a preferential bending line in the absorbent article, thereby allowing the article to bend in a particular direction to more closely fit the wearer's body. The flex bond channel area can also be used as a fluid wicking or fluid transport barrier, which can reduce the possibility of fluid migrating to the periphery of the absorbent article and causing leakage.

[0036] In some respects, disposable absorbent article can comprise following structure (from the surface facing the wearer to the surface facing outward): top sheet, upper nonwoven layer, inner core layer, lower nonwoven layer and back sheet.In some respects, top sheet can be in direct contact with upper nonwoven layer, upper nonwoven layer can be in direct contact with inner core layer, and / or inner core layer can be in direct contact with lower nonwoven layer.So-called " direct contact ", means that there is no other intermediate component layer between the corresponding layers in direct contact with it.But, do not exclude that adhesive material can be arranged between at least a portion of the above-mentioned layers.

[0037] See also Figure 1 and Figure 3 , the absorbent core structure 10 may include an upper nonwoven layer 210 and a lower nonwoven layer 220 (also collectively referred to herein as an upper nonwoven layer and a lower nonwoven layer or an upper nonwoven and a lower nonwoven) and an inner core layer 200 disposed between the upper nonwoven layer 210 and the lower nonwoven layer 220. The absorbent core structure 10 may include an inner core layer 200, which includes a liquid absorbent material. Without being limited by theory, it is believed that the absorbent core structure can recover its dry or wet shape in a certain range of body movements and compressions. The liquid absorbent material may include a matrix comprising cellulose fibers and superabsorbent particles, sometimes referred to herein as "fluff / AGM". The upper nonwoven layer 210 and the lower nonwoven layer 220 may be joined together at the perimeter seal 230 with glue or other conventional bonding methods, including but not limited to ultrasonic bonding, fusion bonding, curling, and combinations thereof.

[0038] The upper nonwoven layer 210 and the lower nonwoven layer 220 can extend outwardly from the inner core layer periphery and can be joined together to form a perimeter seal 230. In some configurations, the entire inner core layer 200 can be located at the inner side of the perimeter seal 230. The perimeter seal 230 can help to seal the absorbent material of the inner core layer 200 in the upper nonwoven layer 210 and the lower nonwoven layer 220. In some configurations, the perimeter seal 230 can extend around the entire inner core layer periphery 200a. In some configurations, the perimeter seal 230 can extend partially around the inner core layer periphery.

[0039] In some configurations, the upper nonwoven layer 210 and the lower nonwoven layer 220 may be discrete materials that can be cut to be approximately the size and shape of the inner core layer 200 so as to fit between the top sheet and the back sheet, but may not substantially extend into the front end region or the rear end region of the absorbent article. In some configurations, the upper nonwoven layer 210 and / or the lower nonwoven layer 220 may extend from the front end region of the absorbent article to the rear end region of the absorbent article.

[0040] The flexibility and / or elasticity of the absorbent core structure causes the absorbent article to conform comfortably to the wearer's anatomical geometry while effectively managing the fluid as it leaves the body. This can be unexpectedly achieved without typical densification hardening (for wet integrity) by utilizing an elastic upper nonwoven layer and lower nonwoven layer composed of an elastic polymer located above and below the loosely packed fluff / AGM matrix of the inner core layer. When the absorbent core structure becomes wet, this absorbent core structure is able to carry structural loads and recover shape without physically hardening or losing desired structural properties.

[0041] It is believed that when the elastic upper nonwoven 210 and lower nonwoven 220 of selection are positioned above and below the fluff / AGM matrix of the inner core layer and are particularly joined to the fluff / AGM matrix and around, in the absorbent core structure rich in cellulose, wet integrity / shape stability is produced, and there is no significant densification and hardening result. Upper nonwoven and lower nonwoven need enough restoring forces to bring the fluff / AGM matrix back to the original state or stable fiber orientation state after compression. Wrapping or encapsulating the fluff core rich in cellulose with simple cellulose tissue or the less elastic nonwoven material may not show enough recovery energy to recover shape in use and particularly when wetting. The structure wet elastic nonwoven described in detail herein can show the recovery energy that is enough to recover the fiber matrix rich in cellulose after compression, and is selected to deliver high compression recovery with relatively low stiffness under dry and wet state.

[0042] It has also been found that absorbent articles comprising flexural bonded channel regions can be produced while maintaining flexibility of the absorbent article in both the transverse and longitudinal directions, thereby allowing the absorbent article to better conform to the body. Without being limited by theory, it is believed that the upper nonwoven can be plastically deformed and maintain the channel structure without the need for permanent compression (densification) of the fluff / AGM of the inner core layer.

[0043] The nonwoven layer of top can have the basis weight of about 30gsm to about 85gsm or about 35gsm to about 70gsm or about 40gsm to about 60gsm.The nonwoven layer of top can have the tensile rigidity of about 0.3N / mm to about 1.6N / mm.The nonwoven layer of top can have the breaking strain greater than about 10% or about 10% to about 50% or about 20% to about 40%.The nonwoven layer of top can have the permanent strain of about 0.005mm / mm to about 0.013mm / mm or 0.005mm / mm to about 0.0090mm / mm.

[0044] The nonwoven layer of the bottom part can have the basis weight of about 10gsm to about 40gsm, or about 15gsm to about 20gsm. The nonwoven layer of the bottom part can have the tensile rigidity of about 0.2N / mm to about 1.6N / mm. The nonwoven layer of the bottom part can have the strain at break greater than about 10%, or about 10% to about 50%, or about 20% to about 40%. The nonwoven layer of the bottom part can have the permanent strain of about 0.005mm / mm to about 0.013mm / mm.

[0045] The upper nonwoven layer and the lower nonwoven layer may include polymer fibers. Suitable upper nonwoven fibers and lower nonwoven fibers may be selected from PET (polyethylene terephthalate), PP (polypropylene), BiCo (bicomponent fibers) selected from PE / PP (PE sheath and PP core) and / or PE / PET (PE sheath PET core), PLA (polylactic acid), and combinations thereof.

[0046] A suitable upper nonwoven layer may comprise from about 60% to about 100%, or from about 70% to about 100%, synthetic fibers, and from about 0% to about 40%, or from about 0% to about 30% regenerated cellulose fibers, such as rayon and / or viscose.

[0047] The upper nonwoven layer can comprise a staple fiber length greater than about 10mm, or greater than about 25mm, or about 10mm to about 100mm, or about 20mm to about 75mm, or about 25mm to about 50mm. The upper nonwoven layer can comprise a fiber having a fiber diameter of about 1.3 dtex to about 10 dtex, or about 1.3 dtex to about 6.0 dtex, or about 2.0 dtex to about 5.0 dtex. In some configurations, the upper nonwoven layer can comprise a fiber having a staple fiber length of about 10mm, or greater than about 25mm, or about 10mm to about 100mm, or about 20mm to about 75mm, or about 25mm to about 50mm. The upper nonwoven layer can comprise a fiber having a fiber diameter of about 1.3 dtex to about 10 dtex, or about 1.3 dtex to about 6.0 dtex, or about 2.0 dtex to about 5.0 dtex. In some configurations, the upper nonwoven layer can comprise a fiber having a fiber diameter of about 2.0 dtex to about 10 dtex.

[0048] The lower nonwoven layer can comprise a fiber having a length greater than about 10mm or greater than about 25mm or about 10mm to about 100mm or about 20mm to about 75mm or about 25mm to about 50mm. In some configurations, the lower nonwoven layer can comprise continuous fibers. The lower nonwoven layer can comprise a fiber having a fiber diameter of about 1.3 dtex to about 5.0 dtex or about 1.3 dtex to about 3.3 dtex, alternatively about 1.3 dtex to about 2.2 dtex or about 2.0 dtex to about 10 dtex. In some configurations, the lower nonwoven layer can comprise a fiber having a fiber diameter of about 0.1 dtex to about 6.0 dtex.

[0049] In some configurations, a suitable fiber combination may include an upper nonwoven polymer fiber having a diameter of about 2.0 dtex to about 10 dtex and a lower nonwoven polymer fiber having a diameter of about 1.7 dtex to about 5 dtex. In some configurations, a suitable fiber combination may include an upper nonwoven polymer fiber having a diameter of about 1.3 dtex to about 2.2 dtex and a lower nonwoven polymer fiber having a diameter of about 1.7 dtex to about 5 dtex.

[0050] The nonwoven layer comprising polymer fibers can maintain its shape and resist plasticization when wetted, and is attached to the fluff / AGM substrate by applying a core construction adhesive, which is directly applied to the fluff / AGM substrate or applied to the elastic nonwoven via conventional spraying, which is selected to achieve bonding but not interrupting the flow of fluid to the fluff / AGM substrate. In addition, the upper nonwoven layer and the lower nonwoven layer can have at least part of the peripheral seal to better connect the upper nonwoven layer and the lower nonwoven layer with the inner core layer included in the upper nonwoven layer and the lower nonwoven layer. The peripheral seal generally comprises at least the middle region of the absorbent article in the region between the inner thighs of the wearer. The presence of a perimeter seal external to the fluff / AGM matrix, where the upper and lower nonwoven layers are bonded by conventional means (e.g., adhesives, polymer welding, and / or strong physical entanglement), helps ensure that the upper and lower nonwovens retain their structural function and do not separate during physical deformation, thereby helping to limit any potential integrity and bunching issues. Creating a perimeter seal that essentially contains the inner core layer allows any excess material to be removed so that the absorbent core structure can be shaped to conform to the inner thigh geometry.

[0051] The nonwoven layer material of suitable upper part and lower part can bend and recover its original shape along with bending force.Thin or highly flexible material is easy to bend under low peak force (load) and low bending energy.Although unsuitable material is easy to bend, it does not have enough recovery energy, and therefore keeps the bending state of deformation due to insufficient recovery energy.Suitable material has enough energy to recover its initial pre-bent state.Material with enough bending recovery energy can be considered as elastic upper nonwoven layer and lower nonwoven layer.

[0052] As described above, the upper nonwoven and the lower nonwoven may include polymer fibers. The polymer fibers may be included to help provide the structural integrity of the upper nonwoven and the lower nonwoven. The polymer fibers may help improve the structural integrity of the upper nonwoven and the lower nonwoven in the machine direction (MD) and the cross direction (CD), which may facilitate web handling during the handling of the upper nonwoven and the lower nonwoven to be incorporated into the pad.

[0053] The polymer fiber of any appropriate component can be selected.Some examples of suitable polymer fibers can include bicomponent fibers or polyethylene terephthalate and copolyethylene terephthalate components comprising polyethylene (PE) and polyethylene terephthalate (PET) components. The components of bicomponent fibers can be configured to sheath-core configuration, side-by-side configuration, eccentric sheath-core configuration, trilobal arrangement or any other desired configuration. In some configurations, polymer fibers can include bicomponent fibers with PE / PET components, which are configured to have concentric sheath-core configurations, wherein the polyethylene component forms a sheath.

[0054] The PE sheath component of the core fiber structure of the sheath core fiber is used to provide the elasticity of the upper nonwoven and the lower nonwoven. In the synergistic combination, the PE sheath component with a lower melting temperature than the PET core component can be used to provide inter-fiber melting / fusion bonding, which is achieved via the thermal treatment of the precursor batt. This can help to provide tensile strength to the web in MD and CD. This inter-fiber bonding can be used to reduce the sliding between the fiber and the fiber, thereby further helping to give the material shape stability and elasticity, even when the material is wetted.

[0055] In the case of relatively high weight fractions of polymer fibers, more connections can be created within the structure via heat treatment. However, too many connection points may impart greater stiffness to the upper and lower nonwovens than desired. For this reason, selecting the weight fraction of polymer fibers may involve prioritizing and balancing the competing demands for stiffness and softness in the upper and lower nonwovens.

[0056] As mentioned above, the upper nonwoven and the lower nonwoven can additionally include polymer fibers, which increase the elasticity of the upper nonwoven and the lower nonwoven. Elastic polymer fibers can help the upper nonwoven and the lower nonwoven to keep permeability and compression recovery. In another configuration, the upper nonwoven and the lower nonwoven can include elastic polymer fibers with variable cross-sections (for example, circular and hollow spirals), and / or can include elastic fibers with different sizes.

[0057] The polymer fiber can be elastic and can be spun from any suitable thermoplastic resin, such as polypropylene (PP), polyethylene terephthalate (PET), or other suitable thermoplastic fibers known in the art. The average staple length of the elastic polymer fiber can be selected to be greater than about 10 mm, about 20 mm to about 100 mm, or about 30 mm to about 50 mm, or about 35 mm to about 50 mm. The elastic polymer fiber can have any suitable structure or shape. For example, the elastic polymer fiber can be circular or have other shapes, such as spiral, fan-shaped elliptical, trilobal, fan-shaped belt, etc. In addition, the elastic polymer fiber can be solid, hollow, or hollow at multiple locations. The elastic polymer fiber can be solid and circular in shape. In other suitable examples, the elastic polymer fiber includes polyester / coextruded polyester fiber. Other suitable examples of elastic polymer fibers can include bicomponent fibers, such as polyethylene / polypropylene, polyethylene / polyethylene terephthalate, polypropylene / polyethylene terephthalate bicomponent fibers. These bicomponent fibers can have a sheath / core configuration.

[0058] Elastic polymer fiber can also be polyethylene terephthalate (PET) fiber or other suitable non-cellulose fibers known in the art.PET fiber can be given any suitable structure or shape.For example, the PET fiber can be round or have other shapes, such as spiral, fan-shaped elliptical, trilobal, fan-shaped belt, hollow spiral, etc.PET fiber can be solid, hollow or multiple hollows.In a specific example, the cross section of PET fiber can be hollow and have a curved or spiral structure along their length.Optionally, elastic polymer fiber can be spirally curled or flatly curled.Elastic polymer fiber can have about 4 to about 12 curls / inch (cpi), or about 4cpi to about 8cpi, or about 5cpi to about 7cpi, or about 9cpi to about 10cpi average curl count.Specific non-limiting examples of elastic polymer fibers can be obtained from Wellman, Inc (Ireland) with trade names H1311 and T5974. Other examples of suitable elastomeric polymer fibers are disclosed in US 7,767,598.

[0059] The reinforcing polymer fibers and the elastic polymer fibers should be carefully selected. For example, although the constituent polymers forming the reinforcing polymer fibers and the elastic polymer fibers may have similarities, the elastic polymer fiber composition should be selected so that the melting temperature of their components is higher than the melting temperature of the bondable components of the reinforcing polymer fibers. Otherwise, during the heat treatment, the elastic polymer fibers may bond to the reinforcing polymer fibers, and vice versa, thereby forming an overly rigid structure. To avoid this risk, where the reinforcing polymer fibers include bicomponent fibers, for example, core-sheath construction fibers having a sheath component with a relatively low melting temperature, at which melting temperature fusion bonding will occur, the elastic polymer fibers may include only the constituent chemical components of the core, which may be a polymer with a relatively high melting temperature.

[0060] Nonwoven performance can be affected by the combination of nonwoven fiber polymer selection, fiber characteristics and fiber arrangement or connection mode. Nonwoven selection can affect the ability of absorbent articles to recover their shape after compression, bending and extension (stretching) forces that exist with body movement in use. If the fibers are short fibers (less than about 10mm), they may be irreversibly rearranged under extension and compression forces. The rearrangement of fibers in the fiber matrix (changing their orientation / state) dissipates the tensile (elongation) or compression force, so that the energy used to affect the deformation is no longer available for recovery to the original shape. Longer fiber networks (usually greater than about 10mm but less than about 100mm) can dissipate the typical tensile / compression forces along the fiber length and through the structure in body movement. Therefore, the applied force can be used to restore the structure to its original state. Longer fiber networks composed of finer fibers (less than about 15 to about 20 microns and about 2.0 dtex) are more likely to stretch and compress. Thus, the fluff / AGM structure can be deformed more easily (and to a greater degree), but the energy associated with these deformations is relatively small and insufficient to bring the structure back to its original state. Thicker fibers (such as greater than about 2.0 dtex to about 10 dtex) are flexible under body forces but provide sufficient fiber and web recovery energy to return the structure to its original state.

[0061] From a structural point of view, the fiber arrangement in the long fiber network can affect the performance of absorbent articles containing these nonwovens. Long fiber webs of thicker fibers are generally more bulky than conventional thin spunbond nonwoven webs composed of closely spaced and physically bonded continuous fine fibers. Webs that produce thicker fibers arranged in a more random orientation (such as those that can be achieved via carding, hydroentanglement, and needle punching) can stretch and compress, whereby the fibers only temporarily adjust their arrangement (there are spaces between the fibers for these arrangements) and can carry / store deformation forces, and this energy can be used to restore the structural shape.

[0062] Additionally, the finer (less than about 2.0 dtex) synthetic fibers (such as BiCo and PP fibers) typically found in spunbond are closely spaced, relatively parallel aligned, and tightly bonded together. The bonded fibers within these spunbond webs are so interconnected (with closely spaced point bonds) that during stretching (elongation), the fibers at the polymer level are forced to stretch, which causes the polymer chains within the fibers to permanently rearrange, and thus the fibers themselves potentially remain permanently elongated (permanently strained) and can no longer recover to their original state.

[0063] In some configurations, the polymer fibers in the upper nonwoven layer and the polymer fibers of the lower nonwoven layer can be different. In some configurations, the polymer fibers of the upper nonwoven layer and the polymer fibers of the lower nonwoven layer can be the same.

[0064] Examples of suitable nonwoven materials include, but are not limited to, the following: (i) 40 gsm carded elastic nonwoven material produced by Yanjan, China (material code; ATB Z87G-40-90), which is a carded nonwoven composed of a blend of 60% 2 dtex and 40% 4 dtex BiCo (PE / PET) fibers. The fibers are bonded (ATB = through "hot" air bonding) to create a wet elastic network. The material basis weight is 40 gsm and has a thickness of about 0.9 mm (at 7 KPa). Without being limited by theory, it is believed that due to the presence of 4 dtex BiCo fibers and a fiber-to-fiber bonded BiCo network, the material has low permanent strain (less than about 0.013 mm / mm) and sufficient dry recovery energy (greater than about 0.03 N*mm) in wet and dry CD ultrasensitive 3-point bend methods; (ii) 55 gsm elastic spunlace material produced by Sandler Germany (Material Code: 53FC041001), which is a hydroentangled nonwoven, which is produced via a carding step (such as the nonwoven described above) followed by hydroentanglement with an elevated drying step (such as described in U.S. Patent Publication No. 2020 / 0315873A1), which produces an entangled and BiCo bonded elastic network. It contains a fiber blend of 30% 10 dtex HS-PET, 50% 2.2 dtex BiCo (PE / PET) and 20% 1.3 dtex rayon. Thus, in both wet and dry CD ultrasensitive 3-point bending methods, the material has low permanent strain (less than about 0.013 mm / mm) and sufficient dry recovery energy (greater than about 0.03 N*mm); and (iii) a 50 gsm elastic spunlace material produced by Sandler Germany (material code: 53FC041005opt82), which is a hydroentangled nonwoven produced via a carding step (such as the nonwoven described above) followed by hydroentanglement with an elevated drying step (as described in U.S. Patent Publication No. 2020 0315873A1), which produces an entangled and BiCo-bonded elastic network. It comprises a fiber blend of 60% 5.8 dtex BiCo (PE / PET), 20% 3.3 dtex trilobal "structural" rayon and 20% 1.3 dtex rayon. Therefore, in the wet and dry CD ultrasensitive 3-point bending method, the material has low permanent strain (less than about 0.013 mm / mm) and sufficient dry recovery energy (greater than about 0.03 N*mm). Although the material has 40% rayon that can be softened when wet, the use of structural trilobal rayon fibers can contribute to structural stability in the wet state.

[0065] In conjunction with adjusting pore size, volume, and number by selecting appropriate fiber size, basis weight, and degree of consolidation, manufacturers may wish to select fiber components with specific surface chemistries, for example, fibers with hydrophobic surfaces, hydrophilic surfaces, or blends of different fibers and / or z-direction stratifications or gradients thereof. Fibers with hydrophilic surfaces will tend to attract and move the aqueous components of menstrual fluid along them in a manner that is conducive to wicking and rapid fluid acquisition after discharge. However, at the same time, the predominance of hydrophilic fiber surfaces within the topsheet may increase the tendency of the topsheet to reacquire fluid (rewet) from the absorbent assembly below, which may result in an undesirable sensation of wetness for the user. On the other hand, fibers with hydrophobic surfaces will tend to repel the aqueous components of menstrual fluid and / or resist the movement of fluid along their surfaces, thereby tending to resist wicking, but also resisting rewetting. For any particular product design, the manufacturer may wish to seek the appropriate balance in selecting constituent fibers having hydrophilic surfaces, fibers having hydrophobic surfaces, or blends and / or z-direction layering thereof, combined with fiber size, fiber consolidation level, and the resulting topsheet pore size, volume, and number.

[0066] like Figure 3As shown, inner core layer 200 is arranged between upper nonwoven layer 210 and lower nonwoven layer 220. Inner core layer 200 is produced in air-laid process. The flow of cellulose fiber and AGM is carried on the fast-moving airflow, and is deposited in the pocket of three-dimensional shape on the rotary forming drum, and the rotary forming drum has vacuum below to suck cellulose and AGM into the pocket in the shelving station. The pocket of this shape provides the actual physical shape of the absorbent core structure. The upper nonwoven or the lower nonwoven can be introduced on the forming drum at first, and they are pulled into three-dimensional pocket shape under vacuum. In this case, cellulose and AGM material flow are directly deposited on the top (or lower nonwoven material) in the forming station. Before entering the forming station, nonwoven is coated with adhesive to provide cellulose and AGM with the stronger connection of nonwoven layer. When leaving the shelving section, the second remaining nonwoven layer is combined with the nonwoven carrying cellulose and AGM layer leaving the shelving section. This second remaining nonwoven (upper nonwoven or lower nonwoven, depending on which nonwoven is advanced through the resting section) is pre-coated with adhesive to achieve perimeter seals and better integrate cellulose and AGM without hindering the flow of liquid into the cellulose and AGM matrix. In another method, the nonwoven is not first introduced into the forming station, and the cellulose and AGM agglomerate is maintained on the forming drum under vacuum until it is sprayed onto the upper nonwoven layer or the lower nonwoven layer with the adhesive applied as described in detail above, and then sealed with the second remaining nonwoven to produce an absorbent core structure. The width of the upper nonwoven web and the lower nonwoven web is selected to be wider than the maximum width of the formed cellulose and AGM matrix, so as to achieve an effective perimeter seal at the junction of the two nonwovens at least on the leftmost and rightmost sides of the absorbent core structure.

[0067] The inner core layer may comprise any of a variety of liquid-absorbent materials commonly used in absorbent articles, such as comminuted wood pulp (commonly referred to as airfelt). One suitable absorbent core material is an airfelt material available from Weyerhaeuser Company (Washington, USA) under the code FR516. Examples of other suitable liquid-absorbent materials that may be used in the absorbent core may include creped cellulose wadding; meltblown polymers including coforms; chemically stiffened, modified or crosslinked cellulose fibers; synthetic fibers such as crimped polyester fibers; peat moss; cotton, bamboo; absorbent polymer materials; or any equivalent material or combination of materials, or mixtures thereof.

[0068] Absorbent polymer materials used in absorbent articles generally comprise water-insoluble, water-swellable, hydrogel-forming, cross-linked absorbent polymers which are capable of absorbing large quantities of liquids and of retaining such absorbed liquids under moderate pressures.

[0069] The absorbent polymer material used in the absorbent core according to the present disclosure may include superabsorbent particles, also referred to as "superabsorbent materials" or "absorbent gelling materials". The absorbent polymer material (usually in particle form) may be selected from polyacrylates and polyacrylate-based materials, such as, for example, partially neutralized, cross-linked polyacrylates. The term "particle" refers to granules, fibers, flakes, spheres, powders, sheets, and other shapes and forms known to those skilled in the art of superabsorbent particles. In some aspects, the superabsorbent particles may be in the shape of fibers, i.e., elongated needle-shaped superabsorbent particles.

[0070] In some configurations, the inner core layer may include cellulose fibers and superabsorbent particles. The inner core layer may include all about 50% to 85% by weight of the inner core layer, or about 55% to about 80%, or about 60% to about 75% cellulose fibers. The inner core layer may include all about 15% to about 50% by weight of the inner core layer, or about 20% to about 40%, or about 25% to about 35% superabsorbent particles. Preferably, the inner core layer may include about 125gsm to about 400gsm cellulose fibers.

[0071] In some configurations, the inner core layer may contain from about 50% to about 85% cellulose fibers and from about 15% to about 50% superabsorbent particles. The resulting absorbent core structure may have a viscosity between about 0.045 g / cm 3 and about 0.15g / cm 3 Between, and / or between 0.045g / cm 3 and 0.12g / cm 3 The absorbent article may have an average density between about 0.045 g / cm 3 and about 0.16g / cm 3 The average density between .

[0072] After the compression step, the absorbent core structure can be compressed and recover their original shape. Suitable absorbent core structures require lower compression forces (less resistance), and when the user compresses and releases the compression forces in a cyclic manner with various body movements, the structure can recover its shape. To achieve this, the structure maintains enough recovery energy after multiple cycles of compression. In the absence of enough recovery energy, the structure remains in a compressed gathered state without enough force (stored energy) to recover.

[0073] like Figure 1 , Figure 2A , Figure 2B , Figure 4 and Figure 5As shown, the absorbent core structure may include a plurality of structural bonding sites 15. The structural bonding sites 15 may be symmetrical and / or asymmetrical and may be any shape, including but not limited to circular, oval, heart-shaped, diamond-shaped, triangular, square, star-shaped and / or X-shaped. The structural bonding sites 15 may be on the absorbent article and / or on the absorbent core structure. In some configurations, the structural bonding sites may have a width of about 2 mm. 2 To about 5mm 2 In some configurations, the total structural bonding area can be about 0.5% to about 5% of the absorbent core structure, or about 0.75% to about 4.5%, or 1% to about 4%, as measured according to the structural bonding site pattern spacing and area measurement method. In some configurations, the total structural bonding area can be about 1% to about 4% of the absorbent article, as measured according to the structural bonding site pattern spacing and area measurement method. The average distance between the structural bonding sites can be about 10mm to about 32mm. In some configurations, the average distance between the structural bonding sites can be greater than about 20mm. In some configurations, the structural bonding sites can have a maximum width of about 1mm to about 6mm, or about 1.5mm to about 5mm, or about 2mm to about 4mm. Not limited by theory, it is believed that the average distance between the structural bonding sites and / or the size of the structural bonding sites can help maintain the structural integrity of the absorbent core structure without producing undesirable rigidity that can inhibit the ability of the absorbent article to conform to the body.

[0074] In some configurations, the structural bonding sites may be distributed across the absorbent article and / or absorbent core structure, or they may be gathered in an area of ​​the absorbent article and / or absorbent core structure. In some configurations, the structural bonding sites may be gathered in the middle area of ​​the absorbent article and / or absorbent core structure. In some configurations, the middle area of ​​the absorbent article and / or absorbent core structure may be free of structural bonding sites and may be surrounded by structural bonding sites and / or embossed areas.

[0075] In some configurations, the structural bonding sites 15 can join the top sheet 110, the upper nonwoven layer 210, the absorbent core structure 10, and the lower nonwoven layer 220. In some configurations, the structural bonding sites 15 can join the upper nonwoven layer 210, the absorbent core structure 10, and the lower nonwoven layer 220.

[0076] Suitable absorbent articles and / or absorbent core structures may include an upper nonwoven layer and a lower nonwoven layer that are closer together in the Z direction at the structural bonding sites, but are not melted together. Since these structural bonding sites are not melted together, they may not be permanent in nature, but may be entangled with the material in the structural bonding sites. In some configurations, the structural bonding sites may be substantially free of fusion bonding.

[0077] While the shape of the structural bonding site may be any shape, suitable shapes may be more elaborate shapes, such as asymmetric shapes (as opposed to simple points).

[0078] The absorbent article 20 can be elastic and conformable and can deliver an excellent use experience without bunching and / or compression. The absorbent article can be exposed to body forces and can return to its original state. The absorbent article can have a resistance between about 0.07 N / mm 2 and 0.30N / mm 2 Between, or about 0.10N / mm 2 To about 0.25N / mm 2 , or about 0.10N / mm 2 To about 0.20N / mm 2 CD dry modulus as measured in wet and dry CD and MD 3-point bend method.

[0079] The absorbent article may have a dry thickness of between about 2.0 mm and about 6.0 mm, or between about 2.0 mm and about 4.5 mm, or from about 2.50 mm to about 4.0 mm, or from about 2.75 mm to about 3.5 mm, as measured according to the wet and dry CD and MD 3-point method. In some configurations, the absorbent article may have a dry thickness of between about 0.07 N / mm 2 and 0.30N / mm 2 and a dry thickness between about 2.0 mm and about 4.5 mm, as measured according to the wet and dry CD and MD 3-point method, or between about 0.10 N / mm 2 To about 0.25N / mm 2 CD dry modulus between about 2.50 mm and about 4.0 mm dry thickness, or between about 0.10 N / mm 2 To about 0.20N / mm 2 The absorbent article may have a CD dry modulus between about 10.0 N*mm and a dry thickness of about 2.75 mm to about 3.5 mm. 2 To about 30.0N*mm 2 , or about 10.0N*mm 2 and about 25.0N*mm 2 , or about 10N*mm 2 To about 20N*mm 2 , or about 13N*mm 2 To about 20N*mm 2 CD dry bending stiffness between about 10.0 N*mm and about 10.0 N*mm, as measured in wet and dry CD and MD 3-point bend method. Particularly suitable absorbent articles include those having a CD dry bending stiffness between about 10.0 N*mm and about 10.0 N*mm. 2 and about 30.0N*mm 2and a dry thickness of about 2.5 mm to about 4.0 mm (as measured according to the wet and dry CD and MD 3-point method), or a CD dry bending stiffness of about 10 N*mm 2 To about 25N*mm 2 and a dry thickness between about 2.5 mm and 4.0 mm, or a CD dry bending stiffness of about 13 N*mm 2 To about 30N*mm 2 And those absorbent articles having a dry thickness of from about 2.75 mm to about 3.5 mm.

[0080] The absorbent article may have a fifth cycle wet recovery energy of about 1.0 N*mm to about 3.5 N*mm, or about 1.5 N*mm to about 3.0 N*mm, or about 1.5 N*mm to about 2.8 N*mm. Particularly suitable absorbent articles may have a fifth cycle wet recovery energy between about 1.0 N*mm and 3.5 N*mm and a fifth cycle wet recovery % of about 29% to about 40%, or a fifth cycle wet recovery energy of about 1.5 N*mm to about 3.0 N*mm and a fifth cycle wet recovery % of about 29% to about 40%, or a fifth cycle wet recovery energy of about 1.5 N*mm to about 2.75 N*mm and a fifth cycle wet recovery % of about 29% to about 40%.

[0081] Absorbent articles composed of absorbent core structures as disclosed herein may also need to deliver a dry touch to consumers after adding fluid, as measured by the touch rewet method. Absorbent core structures and absorbent articles that meet the above characteristics are designed to conform more closely and more completely to the complex anatomical genital shapes of the wearer comfortably and gently. Therefore, such absorbent articles may also need to be dry to the touch after excretion so as not to irritate sensitive genital tissue. Therefore, the absorbent articles described herein may also maintain a touch rewet value of less than about 0.15 grams, or less than about 0.12 grams, or about 0 to about 0.15 grams, or about 0 to about 0.12 grams.

[0082] like Figure 2A and Figure 2BAs shown, the absorbent article 20 also includes a base structure 100, which includes an absorbent core structure 10. The absorbent core structure 10 and / or the inner core layer 200 may include a generally hourglass shape. However, any suitable shape may be utilized. Some examples include an offset hourglass shape (one end is wider than the opposite end, and the middle portion between the two ends is narrowed), a bicycle seat shape (one end and the center portion are narrower than the second end), etc. The side edges 120 and 125 may follow the general contour of the absorbent core structure. Therefore, in the case where the absorbent core structure has an hourglass shape, the side edges of the absorbent articles 120 and 125 may also be arranged in an hourglass shape. However, it is envisioned that the side edges 120 and 125 are generally straight or slightly curved so that they do not follow the contour of the absorbent core structure. Additional details will be discussed below. The absorbent article 20 may be symmetrical about the longitudinal centerline 80 or asymmetrical about the longitudinal centerline 80. Similarly, the absorbent article 20 may be symmetrical about the transverse centerline 90 or asymmetrical about the transverse centerline 90.

[0083] Figure 6 is a cross-sectional view of an absorbent article 20 according to the present disclosure. Fig. 7A and Figure 7B is a top view of an absorbent article 20 according to the present disclosure. Figure 8 yes Fig. 7A An enlarged top view illustration of the flexure bond channel area shown in FIG. Fig. 9 is a perspective view of a flex bond channel area formed in an absorbent article. Fig. 10A and Fig. 10B is along Fig. 7A A partial cross-sectional view of an absorbent article including a flex bond channel area according to various non-limiting embodiments of the present disclosure, taken along line 10-10.

[0084] As mentioned above and as Figure 6 As shown, the absorbent article 20 may include a top sheet 110, a back sheet 130, and an absorbent core structure 10 positioned between the top sheet 110 and the back sheet 130. Fig. 7A As shown, the absorbent article 20 may also include one or more flexure bonded channel areas 160. At least some or all of the flexure bonded channel areas 160 may be permanent channels, meaning that their integrity is at least partially maintained both in a dry state and in a wet state. The flexure bonded channel areas 160 may be continuous depressions and / or may include a series of individually compressed, closely spaced flexure bonded embossments.

[0085] The flexure bond channel area 160 may have any configuration, for example, one or more linear shapes extending along the longitudinal centerline 80, one or more curved shapes approximately along the longitudinal centerline 80, an elliptical shape, a rectangular shape, a triangular shape, a polygonal shape, or any other shape. In some configurations, the flexure bond channel area 160 may extend substantially longitudinally, meaning that each flexure bond channel area extends more in the longitudinal direction than in the transverse direction, or extends at least twice as much in the longitudinal direction than in the transverse direction (as measured after projecting onto the corresponding axis). In some configurations, the flexure bond channel area 160 may extend substantially transversely, meaning that each flexure bond channel area extends more in the transverse direction than in the longitudinal direction, or extends at least twice as much in the transverse direction than in the longitudinal direction (as measured after projecting onto the corresponding axis).

[0086] In some configurations, the absorbent article 20 may include an inner flex bond channel area 161 and an outer flex bond channel area 162. The inner flex bond channel area 161 and the outer flex bond channel area 162 may be used as hinge structures in the absorbent article, which may help enable the absorbent article to flex longitudinally and laterally and thereby better conform to the wearer's anatomical structure. The inner flex bond channel area 161 and the outer flex bond channel area 162 may also be used as visual signals of a fluid barrier.

[0087] The inner flex bond channel area 161 can be curved and / or arcuate and can extend substantially parallel to the longitudinal centerline 80 of the absorbent article. In other configurations, the inner flex bond channel area 161 can be substantially straight. In some configurations, the inner flex bond channel area 161 can be concave toward the longitudinal centerline 80, such as Figure 7B 161 ', such that they curve toward the longitudinal centerline 80. The interior flex bond channel areas 161 may also be convex such that they curve away from the longitudinal centerline 80, or have any other suitable arrangement.

[0088] The absorbent article 20 and the absorbent core structure 10 each include a front end region 21, a rear end region 23, and a middle region 22 disposed between the front end region and the rear end region. The middle region 22 may include a central use area 175. An internal flex bond channel region 161 may be present in the middle region 22 or a portion thereof and a portion of the front end region 21 and / or the rear end region 23. In some configurations, the internal flex bond channel region 161 may extend longitudinally from the front end region 21 to the rear end region 23. The absorbent article 20 may include one or more internal flex bond channel regions 161, such as two, three, four, five, or six.

[0089] In some configurations, the internal flex bond channel region 161 can be positioned in at least the middle region 22 and can form a closed loop substantially surrounding the central use area 175, such as Fig. 7A In some configurations, the absorbent article may include a pair of internal flex bond channel areas 161, 161', wherein at least a portion of the central use area 175 is disposed between the pair of internal flex bond channel areas. When present in a symmetrical pair relative to the longitudinal centerline 80, the internal flex bond channel areas 161, 161' may be spaced apart from one another across their entire longitudinal dimension (e.g., as shown in FIG. 1 ). Figure 7B ). In some configurations, the internal flexure bonding channel areas 161 may be spaced apart by a distance of at least about 10 mm so as not to impart local stiffness in the space between the internal flexure bonding channel areas. In some configurations, the distance between the internal flexure bonding channel areas may be about 10 mm to about 45 mm, or about 12 mm to about 30 mm, or about 15 mm to about 25 mm, as measured from the inner edge of one internal flexure bonding channel area to the inner edge of the opposite internal flexure bonding channel area in a direction parallel to the transverse centerline 90.

[0090] The absorbent article may include structural bonding sites 15 and flex bond channel areas 160. In some configurations, the central use area 175 may be substantially free of structural bonding sites 15 and may be at least partially surrounded by areas of structural bonding sites and / or flex bond channel areas, such as Fig. 7A It should be understood that Figure 7B The absorbent article shown in may also include structural bonding sites 15 as described above.

[0091] like Fig. 7A and Figure 7B As shown, the absorbent article 20 may include an outer flex bond channel area 162 to further increase the flexibility and fit of the absorbent article and / or to help provide a visual signal of a fluid barrier. The above description of the flex bond channel area 160 and / or the inner flex bond channel area 161 may also apply to the outer flex bond channel area 162. In some configurations, in order to reduce the risk of fluid leakage, the outer flex bond channel area 162 may be positioned between the absorbent core structure periphery 10a and the inner core layer periphery 200a, such as, for example Fig. 7A. The outer flexure bond channel area 162 can be positioned outside the inner core layer periphery 200a and can at least partially surround the inner core layer 200. In such a configuration, the outer flexure bond channel area 162 can compress the top sheet and the upper nonwoven layer toward the lower nonwoven layer without the inner core layer in between. In some configurations, the distance between the outer edge of the outer flexure bond channel area 162 and the absorbent core structure periphery 10a can be at least 3mm, or about 3mm to about 8mm, or about 5mm to about 6mm. In other configurations, such as for example Figure 7B As shown, the outer flex bond channel area 162 can be positioned inboard of the inner core layer perimeter 200a and can compress the topsheet, upper nonwoven layer, and inner core layer toward the lower nonwoven layer.

[0092] In some configurations, the outer flex bond channel region 162 may include a closed loop around the inner flex bond channel region 161. In such a configuration, Fig. 7A As shown, the distance "X" between the inner flexure bond channel area 161 and the outer flexure bond channel area 162 can be about 10 mm to about 30 mm, or about 12 mm to about 25 mm, or about 15 mm to about 20 mm, as measured from the inner edge of the outer flexure bond channel area 162 to the outer edge of the inner flexure bond channel area 161 in a direction parallel to the transverse centerline 90. In other configurations, the outer flexure bond channel area 162 may include a pair of outer flexure bond channel areas positioned outside the inner flexure bond channel area 161. In such a configuration, the distance between the inner flex bond channel area 161 and the outer flex bond channel area 162 can vary along the longitudinal length of the inner flex bond channel area 161 and the outer flex bond channel area 162, wherein the maximum distance X' between the inner flex bond channel area 161 and the outer flex bond channel area 162 is from about 4 mm to about 15 mm, or from about 6 mm to about 12 mm, or from about 8 mm to about 10 mm, as measured from the outer edge of the outer flex bond channel area 162 to the outer edge of the inner flex bond channel area 161 in a direction parallel to the transverse centerline 90. In some configurations, the inner flex bond channel area 161 can be concave and the outer flex bond channel area 162 can be convex, which can help improve the fit of the absorbent article by allowing the intermediate area to be closer to the wearer's anatomy.

[0093] like Figure 7BAs shown, absorbent article may include one or more transverse second flexure bonding channel areas 170. Transverse second flexure bonding channel areas 170 may orient their longer dimensions primarily in the transverse direction, or even substantially perpendicular to the longitudinal centerline 80 of absorbent article 20. Transverse second flexure bonding channel areas 170 may be used as transverse hinge structures that may enable absorbent article to be transversely flexed and thus conform to the wearer's anatomical structure, and / or may be used as visual barrier features. The description of the flexure bonding channel area 160 provided herein may also be applicable to the transverse second flexure bonding channel area 170. Transverse second flexure bonding channel areas 170 may be arranged in the front end area 21, the middle area 22 and / or the rear end area 23. Transverse second flexure bonding channel areas 170 may have any configuration, for example, one or more linear shapes extending along the transverse centerline 90, one or more curved shapes roughly along the transverse centerline 90, elliptical shapes, rectangular shapes, triangular shapes, polygonal shapes, inverted V shapes or any other shapes. In some configurations, the transverse second flexure bond channel area 170 may be positioned longitudinally outward of the outer flexure bond channel area 162 and / or the inner flexure bond channel area 161. The transverse second flexure bond channel area 170 may have a length of about 10 mm to about 60 mm, or about 15 mm to about 40 mm, or about 25 mm to about 35 mm, as measured along the curve of the second flexure bond channel area from the first end of the channel area of ​​the second flexure bond channel area to the second end of the second flexure bond channel area. In some configurations, the transverse second flexure bond channel area 170 may be different and separate from the inner flexure bond channel area 161 and the outer flexure bond channel area 162, such as Figure 7B The proposed.

[0094] Still see Figure 7B, the absorbent article 20 may include a front flexure bond channel area 190 positioned in the front end region 21 and / or a rear flexure bond channel area 192 formed in the rear end region 23. The description of the flexure bond channel area 160 provided herein may also apply to the front flexure bond channel area 190 and / or the rear flexure bond channel area 192. The front flexure bond channel area 190 and the rear flexure bond channel area 192 may be generally u-shaped and may be positioned outside the inner flexure bond channel area 161, the outer flexure bond channel area 162, and / or the transverse second flexure bond channel area 170. In some configurations, the front flexure bond channel area 190 may extend from the front end region 21 to a position adjacent to the outer flexure bond channel area 162 in the middle region 22. In some configurations, the rear flexure bond channel area 192 may extend from the rear end region 23 to a position adjacent to the outer flexure bond channel area 162 in the middle region 22. As shown, the front flex bond channel area 190 and the rear flex bond channel area 192 may be discontinuous, e.g., discrete, and may not be joined to the outer flex bond channel area 162 or the inner flex bond channel area 161. It is believed that the front flex bond channel area 190 and the rear flex bond channel area 192 may help provide comfort and conformability to the absorbent article 20 in the front end region 21 and the rear end region 23.

[0095] The flexure bonding channel area 160 can be continuous or discontinuous. In this article, "discontinuous" means that the flexure bonding channel area can be separated by the non-channel area (that is, the area without forming a channel). The distance between two successive flexure bonding channel areas (that is, the length of the non-channel part) can be changed according to product design. Not limited by theory, it is believed that by having a non-channel area between, for example, the end of the front flexure bonding channel area 190 and the outer flexure bonding channel area 162 or between the inner flexure bonding channel area 161 and the outer flexure bonding channel area 162, it can help to avoid producing undesirable rigidity, and can help to provide the improved flexibility and the conformability of absorbent articles.

[0096] In some configurations, the internal flexure bonding channel area 161 and / or the external flexure bonding channel area 162 can be continuous. In some configurations, the internal flexure bonding channel area 161 can be discontinuous, and the external flexure bonding channel area 162 can be continuous. The flexure bonding channel area 160 can have a minimum channel length of about 50mm, as measured from the first end of the flexure bonding channel area to the second end of the flexure bonding channel area along the curve of the flexure bonding channel area. Not limited by theory, it is believed that if the flexure bonding channel area is less than about 50mm, the length in the flexure bonding channel area may not be enough to provide enough multi-directional flexibility to produce the desired bending in absorbent articles to allow absorbent articles to fit closely to the body. It is believed that the channel length is that the flexure bonding channel area of ​​at least 50mm can fully affect adjacent non-channelized areas, so that absorbent articles can be conformable and fit closely to the body. The flex bond channel area 160 may have a length of about 50 mm to about 400 mm, or about 60 mm to about 350 mm, or about 75 mm to about 300 mm, or about 100 mm to about 200 mm.

[0097] In some configurations, the inner flex bond channel region 161 may form a closed loop defining a central channel area 180, such as, for example Fig. 7A The central channel zone 180 may have a longitudinal length "LZ" as measured in a direction parallel to the longitudinal axis from a first outermost point of the inner flexure bond channel area 161 to a longitudinally opposite second outermost point of the inner flexure bond channel area 161. The longitudinal length "LZ" of the central channel zone may be from about 50% to about 90% of the inner core longitudinal length "LC", or from about 60% to about 75% of the inner core longitudinal length "LC".

[0098] In some configurations, the flex bond channel region 160 can have a channel area of ​​about 10% to about 20% of the area of ​​the inner core layer.

[0099] See also Figure 8, the flexure bonding channel area 160 may include a plurality of closely spaced flexure bonding embossings 160a. The flexure bonding landing area 163 is arranged between adjacent flexure bonding embossings 160a. The flexure bonding embossings 160a may have an embossing length "L" of about 1.0mm to about 4.0mm, or about 1.5mm to about 3.75mm, or about 2.0mm to about 3.5mm, as measured according to the flexure bonding embossing length method. The flexure bonding channel embossings 160a may have a width "W1" of between about 1.0mm to about 3.0mm, or about 1.25mm to about 2.5mm, or about 1.5mm to about 2.0mm at the top surface of the top sheet. The length "S" of the flex bond landing area 163 between adjacent flex bond embossments 160a may be from about 0.5 mm to about 4 mm, or from about 1.0 mm to about 3 mm, or from about 1.5 mm to about 2.5 mm, as measured according to the Flex Bond Land Area Length Method. Without being limited by theory, it is believed that the combination of the flex bond embossment length and width and / or the flex bond land area length "S" between flex bond embossments may allow the flex bond channel area to bend / flex in multiple directions and provide a consumer preferred visual barrier while still maintaining the overall flexibility and conformability of the absorbent article.

[0100] In some configurations, the flex bond embossment 160a can extend substantially parallel to the longitudinal centerline 80 of the absorbent article. In other configurations, the flex bond embossment 160a can extend substantially parallel to the transverse centerline 90 of the absorbent article.

[0101] In some configurations, the flex bond embossments 160a may be evenly spaced. In some configurations, at least a portion of the flex bond embossments 160a may be grouped into clusters of two, three, or four or more flex bond embossments, such as Figure 7B As shown, and the spacing between the clusters can be from about 2mm to about 8mm, or from about 3mm to about 6mm. Without being limited by theory, it is believed that such flexure bonded embossed clusters can help provide increased flexibility in the lateral and longitudinal directions to the flexure bonded channel area, and / or can help improve fluid handling, because fluid may be able to flow through the spacing between the clusters to reach other areas of the absorbent core structure.

[0102] Fig. 9A perspective view of a diagram of a flexure bonding channel area 160 in an absorbent article is shown, wherein the flexure bonding channel area 160 includes a plurality of flexure bonding embossings 160a. The thickness "T2" of the flexure bonding landing area 163 may be between about 50% to about 70% of the thickness "T" of the absorbent article. Without being limited by theory, it is believed that reducing the thickness of the absorbent article in the z direction along the length of the flexure bonding channel area (including in the flexure bonding landing area) may help to produce an effective preferential bending line that allows the absorbent article to conform closely to the body at a preferred position and / or helps to produce an effective visual barrier feature that is easily visible to the user. Non-channelized area 172 is located near the flexure bonding channel area 160. The flexure bonding embossing 160a may have an embossed area between about 22% to about 65% of the flexure bonding channel area area.

[0103] Compared with the flexure bonding channel area described herein, the current absorbent article for menstrual application may include a series of point-shaped depressions, whereby the material between the depression points in the z direction is restored to the uncompressed thickness of the non-channelized area to a great extent. In such a structure, the channel depth between the depression points may be less than about 10% to about 25% of the channel depth at the embossing point. Without being limited by theory, it is believed that such point-shaped depressions may not produce effective bending lines to allow the article to be closely conformed to the body. Other current absorbent articles may include small physical bonding points with relatively large spacing between the bonding points. Without being limited by theory, it is believed that if the physical bonding points are relatively small (e.g., width is less than about 0.5mm) and well spaced (e.g., greater than about 1mm-4mm), these physical bonding points will not be enough to reproducibly drive the fit / bending direction of the absorbent article. In order to establish a reproducible, effective fit / bending direction, it is believed that enough mass should be displaced in the z direction, and a considerable portion through the channel area should have consistent thinning to effectively drive a preferred and consistent bending feature portion.

[0104] Typically, the flexure bond channel area 160 can be formed by applying a compressive force to the top sheet 110, the upper nonwoven layer 210, the inner core layer 200 and the lower nonwoven layer 220. The top sheet at the flexure bond channel area is pushed downward into the absorbent core structure, and the materials of the top sheet and the absorbent core structure are compressed at the bottom of the flexure bond channel area and below the bottom. Through this operation (commonly referred to as "embossing process"), the flexure bond channel area of ​​the absorbent article has a relatively higher density than the non-channelized area. As a result of compression, the flexure bond channel area 160 can be formed into a groove-like shape with an elongated depression, such as a pair of opposite side walls 165 and a bottom surface 166, such as Fig. 10A and Fig. 10B shown.

[0105] In some configurations, compressive forces are applied to the topsheet 110, upper nonwoven layer 210, and lower nonwoven layer 220 to create flex bond channel regions 160 in areas without an inner core layer. The flex bond channel regions of the present disclosure may be formed by any structure and process known in the art.

[0106] The flex bond channel region 160 may be formed by applying a uniform (or single level) of compressive force. In some configurations, the flex bond channel region 160 may be formed by applying two or more levels of compressive force, thereby forming a step channel structure, such as disclosed in, for example, U.S. Pat. No. 6,563,013. In a step channel configuration, the flex bond channel region may include opposing sidewalls, a first portion forming a first bottom surface, and a second portion forming a second bottom surface, wherein the second bottom surface is below the first bottom surface, and the second portion may be discrete and may be surrounded by the first portion.

[0107] See also Fig. 10A and Fig. 10B , the wearer-facing surface 20A of the absorbent article 20 may include a flexure bonding channel area 160 with a dry channel depth "D", as measured according to the flexure bonding channel depth method. The dry channel depth "D" of the flexure bonding channel area 160 may be from about 1.0mm to about 4.0mm, or from about 1.5mm to about 3.5mm, or from about 2.0 to about 3.0mm. The flexure bonding channel area may have a channel depth of at least 1.0mm. In some configurations, the dry channel depth "D" of the flexure bonding channel area 160 may be between about 20% to about 80% of the absorbent article thickness "T", or between about 25% to about 70% of the absorbent article thickness "T". The absorbent article thickness is measured according to the flexure bonding channel depth method. Without being limited by theory, it is believed that the flexure bonding channel area 160 with a dry channel depth as described herein can provide improved body fit, good fluid barrier and / or aesthetic visual barrier effect.

[0108] See also Fig. 10BIn some configurations, the outward-facing surface 20B of the absorbent article 20 may have a flexure bond depression area 164 having a dry channel depth "D1" as measured from the surrounding area of ​​the outward-facing surface 20B to the flexure bond depression bottom wall 168. The dry channel depth "D1" of the flexure bond depression area 164 may be from about 1.0 mm to about 4.0 mm, or from about 1.5 mm to about 3.5 mm, or from about 2.0 to about 3 mm. In certain configurations, the dry channel depth "D1" of the flexure bond depression area 164 in the outward-facing surface 20B may be between about 15% and about 80% of the absorbent article thickness "T", or between about 25% and about 70% of the absorbent article thickness "T". Although the outward-facing surface 20B of the absorbent article 20 may not directly contact the embossing device during embossing, the flexure bond depression area 164 may be produced. Without being limited by theory, it is believed that the flexure bond depression area 164 in the outwardly facing surface 20B can be formed by the tensioning of the top sheet and absorbent core structure. After embossing and removing the embossing device, the recovery of the material forming the top sheet and absorbent core structure can pull or pull back the material upwards toward the wearer-facing surface 20A.

[0109] The flex bond channel area 160 may have a channel thickness "T1" of less than about 2.5 mm, or about 0.5 mm to about 2.5 mm, or about 1.0 mm to about 2.0 mm.

[0110] The flex bond channel area 160 may have a channel width "A" at the base of the channel of about 1.0 mm to about 3.0 mm, or about 1.25 to about 2.5 mm, or about 1.5 to about 2.0 mm, as measured according to the flex bond channel width method. The flex bond recessed area 164 may have a transverse channel width "A" at the base of the recess of between about 1.0 mm to about 3.0 mm, or about 1.25 mm to about 2.5 mm, or about 1.5 mm to about 2.0 mm.

[0111] In some configurations, the maximum width of the structural bonds 15 may be greater than the channel width "A" of the flex bond channel areas 160. Without being limited by theory, it is believed that if the channel width "A" of the flex bond channel areas 160 is greater than the maximum width of the structural bonds 15, a stiffness may be created that may hinder the ability of the absorbent core structure and / or absorbent article to conform closely to the body.

[0112] The flex bond channel region 160 may have a thermal conductivity of less than about 0.3 g / cm 3 , or about 0.05g / cm 3 To about 0.3g / cm 3 , or about 0.1g / cm 3 To about 0.25g / cm 3Without being limited by theory, it is believed that the channel density is less than about 0.3 g / cm 3 The channel density causes the inner core layer to plastically deform so that the flex bond channel area is maintained in a compressed state, but still allows the flex bond channel area to flex in the transverse and longitudinal directions.

[0113] As measured according to the flexure bonding channel MD bending resistance method, the flexure bonding channel area 160 can have a dry MD bending resistance of less than about 0.04N / mm, or about 0.005N / mm to about 0.035N / mm, or about 0.1N / mm to about 0.030N / mm. Not limited by theory, it is believed that the flexure bonding channel area with a dry MD bending resistance greater than about 0.04N / mm can produce stiffness, which can hinder the ability of the absorbent core structure and / or absorbent article to conform closely to the body in the longitudinal direction and the transverse direction at the same time.

[0114] The flexure bonding channel region 160 may have a dry flexure bonding CD bending resistance of about 0.005 N / mm to about 0.30 N / mm, or about 0.01 N / mm to about 0.25 N / mm. The flexure bonding channel region may have a CD bending resistance index of about 1.1 to about 3.0, about 1.2 to about 2.5, or about 1.5 to about 2.0.

[0115] Top sheet

[0116] The top sheet 110 may be formed of any suitable nonwoven web or formed film material. Referring back to the drawings, the top sheet 110 is positioned adjacent to the wearer-facing surface 20A of the absorbent article 20 and may be joined thereto and to the back sheet 130 by any suitable attachment or bonding method. The top sheet 110 and the back sheet 130 may be directly joined to each other in a peripheral region outside the periphery of the absorbent core structure and may be indirectly joined by directly joining them to the wearer-facing surface and the outward-facing surface of the absorbent article, respectively, or to an additional optional layer included in the absorbent article.

[0117] The absorbent article 20 can have any known otherwise effective top sheet 110, such as a compliant, soft-feeling, and non-irritating top sheet to the wearer's skin. Suitable top sheet materials will include liquid-permeable materials that are comfortable when in contact with the wearer's skin and allow discharged menstrual fluid to penetrate quickly through. Some suitable examples of top sheet materials include films, nonwovens, and laminate structures having film / nonwoven layers, film / film layers, and nonwoven / nonwoven layers.

[0118] Non-limiting examples of nonwoven web materials that may be suitable for use as topsheet 110 include fibrous materials made from natural fibers, modified natural fibers, synthetic fibers, or combinations thereof. Some suitable examples are described in U.S. Pat. Nos. 4,950,264, 4,988,344, 4,988,345, 3,978,185, 7,785,690, 7,838,099, 5,792,404, and 5,665,452.

[0119] The top sheet 110 can be compliant, feel soft, and non-irritating to the wearer's skin. In addition, the top sheet 110 can also be liquid permeable, thereby allowing liquid (e.g., urine, menstrual fluid) to easily penetrate its thickness. Some suitable examples of top sheet materials include films, nonwovens, and laminate structures with film / nonwoven layers, films / film layers, and nonwoven / nonwoven layers. Other exemplary top sheet materials and designs are disclosed in U.S. Patent Application Publications 2016 / 0129661, 2016 / 0167334, and 2016 / 0278986.

[0120] In some examples, top sheet 110 may include tufts, such as described in US 8,728,049, US 7,553,532, US 7,172,801, US 8,440,286, US 7,648,752, and US 7,410,683. Top sheet 20 may have a pattern of discrete hair-like fibrils such as described in US 7,655,176 or US 7,402,723. Additional examples of suitable top sheet materials include those described in US 8,614,365, US 8,704,036, US 6,025,535, and U.S. Patent Publication No. 2015 / 041640. Another suitable top sheet may be formed by a three-dimensional substrate, such as described in detail in US 2017 / 0258647. The topsheet may have one or more layers as described in U.S. Patent Publication Nos. 2016 / 0167334; US 2016 / 0166443 and US 2017 / 0258651.

[0121] In some examples, the top sheet 110 can be formed of a nonwoven web material of a spunbond web, the spunbond web comprising a monocomponent continuous fiber, or alternatively, a bicomponent or multicomponent fiber, or a blend of monocomponent fibers spun from different polymer resins, or any combination thereof. The top sheet can also be a formed nonwoven top sheet, as disclosed in U.S. Patent Publication No. 2019 / 0380887.

[0122] In order to ensure that the fluid contacting the top (wearer-facing) surface of the top sheet will move appropriately and quickly in the z direction to the bottom (outward-facing) surface of the top sheet, where the fluid can be sucked into the absorbent article, it is important to ensure that the nonwoven web material forming the top sheet has an appropriate weight / volume density, thereby reflecting the appropriate presence of interstitial channels (sometimes referred to as "pores") among and between the constituent fibers, through which the fluid can move in the nonwoven material. In some cases, the nonwoven material with fibers that are too densely consolidated may have pores of insufficient number and / or volume and / or size, and the nonwoven material will block rather than promote the rapid downward fluid movement in the z direction. On the other hand, the nonwoven material with fibers that are too large and / or consolidated to provide a certain degree of opacity (for the purpose of hiding the absorbed fluid in the layer below) and a significant appearance may be perceived negatively by the user.

[0123] The thickness of the topsheet material can be controlled to balance the competing demands for opacity and bulk (which require higher thickness) with the limitation of the z-direction distance that discharged fluid can travel from the wearer-facing surface through the topsheet to the outward-facing surface to reach the absorbent core component below. Therefore, it may be desirable to control the manufacture of the topsheet material to produce a topsheet material having a thickness of about 0.20 mm to about 1.0 mm, or about 0.25 mm to about 0.80 mm, or about 0.30 mm to about 0.60 mm.

[0124] Second top sheet (STS)

[0125] In some cases, an STS layer may be included between the topsheet and the absorbent core structure to enable the absorbent core structure to easily receive a sudden discharge of fluid and, after receiving it, wick the fluid in the x and y directions to distribute the fluid over the underlying absorbent core structure.

[0126] If included, the STS can be a nonwoven fibrous structure that can include cellulosic fibers, non-cellulosic fibers (e.g., fibers spun from polymer resins), or blends thereof. To accommodate the folding and lateral gathering of the absorbent article 20 and absorbent core structure 10, as described herein, the STS can be formed of a relatively flexible (i.e., having a relatively low bending stiffness) material.

[0127] Many specific examples of suitable STS compositions and structures and their combinations with suitable topsheet compositions and structures are further described in U.S. Patent Serial Nos. 16 / 831,862, 16 / 831,854, 16 / 832,270, 16 / 831,865, 16 / 831,868, 16 / 831,870, and 16 / 831,879, and U.S. Provisional Application Serial Nos. 63 / 086,610 and 63 / 086,701. Additional suitable examples are described in US 9,504,613; US2012 / 040315; and US2019 / 0021917.

[0128] In some configurations, the absorbent article may be free of a secondary topsheet.

[0129] Negatives

[0130] Backsheet 130 can be positioned below or near the outwardly facing surface of absorbent core structure 10 and can be joined thereto by any suitable attachment method. For example, backsheet 130 can be fixed to absorbent core structure 10 by an array of separate lines, spirals or points of uniform continuous adhesive layer, patterned adhesive layer or adhesive. Additionally, attachment method can include thermal bonding, pressure bonding, ultrasonic bonding, dynamic mechanical bonding or any other suitable attachment mechanism or combination thereof. In other examples, it is conceivable that absorbent core structure 10 is not directly joined to backsheet 130.

[0131] Backsheet 130 can be impermeable or substantially impermeable to aqueous liquid (for example, urine, menstrual fluid), and can be made of thin plastic film, although other liquid impermeable flexible materials can also be used.As used herein, term "flexible" refers to compliant and easily conformable to the material of the general shape and outline of human body.Backsheet 130 can prevent or at least substantially suppress absorption and be contained in the fluid in absorbent core structure 10 to escape and arrive at the clothing article of the wearer that can contact absorbent article 20, such as underwear and outer garment.However, in some cases, backsheet 130 can be made into and / or be suitable for allowing steam to escape (that is, backsheet is made into breathable) from absorbent core structure 10, and in other cases, backsheet 130 can be made so as not to allow steam to escape (that is, it is made into impermeable).Therefore, backsheet 130 can comprise polymer film, such as the thermoplastic film of polyethylene or polypropylene. Suitable materials for backsheet 130 are, for example, thermoplastic films having a thickness of about 0.012 mm (0.5 mil) to about 0.051 mm (2.0 mil).Any suitable backsheet known in the art may be used in the present invention.

[0132] Some suitable examples of materials suitable for forming the backsheet are described in US 5,885,265, US 4,342,314 and US 4,463,045. Suitable single layer breathable backsheets for use herein include those described in GB A 2184 389, GBA 2184 390, GB A 2184 391, US 4,591,523, US 3,989,867, US 3,156,242, WO 97 / 24097, US 6,623,464, US 6,664,439 and US 6,436,508.

[0133] The backsheet 130 may have two layers: a first layer comprising a vapor permeable apertured formed film layer and a second layer comprising a breathable microporous film layer, as described in US 6,462,251. Other suitable examples of double or multilayer breathable backsheets for use herein include those described in US 3,881,489, US 4,341,216, US 4,713,068, US 4,818,600, EP 203821, EP 710 471, EP 710 472 and EP 0793 952.

[0134] Other features

[0135] In some configurations, the absorbent article 20 may be provided with an adhesive deposit to provide a mechanism for the user to adhere the absorbent article to the inside of her panties in the crotch region thereof. When the absorbent article 20 is packaged for shipping, handling, and storage prior to use, the adhesive deposit may be covered by one or more sheets of a release film or paper (not shown) that covers / shields the adhesive deposit from contact with other surfaces until the user is ready to remove the release film or paper and place the absorbent article in her panties for wear / use.

[0136] In some configurations, the absorbent article 20 may include opposing wing portions 140, 150 ( Figure 2A), the wing portions extending transversely beyond the longitudinal edges of the absorbent portion of the absorbent article, with a width dimension relatively larger than the width dimensions of the front and rear portions of the absorbent article. Wings are currently commonly provided with feminine hygiene absorbent articles. As provided, they typically have an adhesive deposit applied to their outwardly facing surface (which is facing outward before the absorbent article is placed in the user's underwear and the wings are applied). The wing portions may also include an adhesive deposit as described above, which enables the user to wrap the wing portions through the leg openings of the underwear and around the inside edges thereof, and adhere the wing portions to the outwardly facing surface / underside of the underwear in the crotch area, thereby providing additional retention support for the absorbent article and helping to protect the underwear from soiling near its leg edges.

[0137] Test Method

[0138] Layer of interest

[0139] For any of the following methods where not all component layers of the article are tested, cryo spray may be used, if desired, to separate the layer of interest from the layers not being tested.

[0140] Fracture strain method

[0141] The force-to-displacement behavior of the sample is measured on a universal constant-rate extension test frame (a suitable instrument is MTS Alliance using TestSuite software, available from MTS Systems Corp., Eden Prairie, MN, or its equivalent) equipped with a load cell, and the measured force is within 1% to 99% of the limit of the load cell. The sample is stretched at a constant rate (mm / sec) until it breaks, and the percent strain at break is measured. All tests are conducted in a room controlled at 23°C ± 3°C and 50% ± 2% relative humidity, and the test samples are conditioned in this environment for at least 2 hours prior to testing.

[0142] The grips used to hold the test specimens are lightweight (<80 grams), vise action grips with semi-cylindrical steel to rubber coated steel gripping faces at least 40 mm wide. The grips are mounted on a universal test frame and are mounted so that they are aligned horizontally and vertically with each other.

[0143] The test specimens were prepared as follows. If necessary, the test material was obtained by cutting the test material from the absorbent article. When the test material was cut, no contamination or deformation was caused to the material layer during the process. The test specimens were cut from areas without any folds or wrinkles on the test material. The test specimens were 100 mm long (parallel to the transverse axis, or the intended transverse axis of the article) and 25.4 mm wide (parallel to the longitudinal axis, or the intended longitudinal axis of the article). In a similar manner, five replicate test specimens were prepared.

[0144] The universal test frame is prepared as follows. The initial grip-to-grip spacing distance is set to a nominal gauge length of 80 mm, and the grips are then zeroed. The test frame is programmed to move the grips closer together with an intentional relaxation of 1 mm to ensure that there is no pre-tension on the test specimen at the beginning of the test. (During this movement, the specimen will become relaxed between the grips). Next, the grips will move apart at a relaxation rate of 1 mm / s until a relaxation preload of 0.05 N is exceeded. (At this point, the grip position signal is used to calculate sample relaxation, the adjusted gauge length, and the strain is defined as zero, 0.0). The grips will then move apart at a rate of 1 mm / s until the sample breaks or the extension limit of the instrument is exceeded.

[0145] The test was performed by inserting the test specimen into the grips so that the long axis of the specimen was parallel and centered with the movement of the grips. The test was started and force ("load") and displacement data were continuously collected at a data acquisition rate of 100 Hz.

[0146] Plot a graph of load (N) versus displacement (mm). Determine the peak load from the curve and then determine the fracture sensitivity as follows. Determine the chuck position at which the load signal decreases by 75% after reaching the peak load and record it as the final length of the specimen (Lf) to the nearest 0.01 mm. The initial length of the specimen is defined by the chuck position when the relaxation preload of 0.05 N is exceeded, and this value is recorded as the initial length of the specimen (Li) to the nearest 0.01 mm. Calculate the fracture strain percentage as follows and record it to the nearest 1%.

[0147] % Fracture strain = ((Lf-Li) / Li)*100

[0148] In a similar manner, repeat this procedure for all five replicate test specimens. Calculate the arithmetic mean of the % Strain at Break for the five replicate test specimens and report as % Strain at Break to the nearest 1%.

[0149] Wet and dry CD and MD 3-point bending method

[0150] The bending properties of the absorbent article test specimens are measured on a universal constant rate extension test frame (a suitable instrument is MTS Alliance using TestSuite software, available from MTS Systems Corp., Eden Prairie, MN, or its equivalent) equipped with a load cell, and the measured force is within 1% to 99% of the limit of the load cell. The test is performed on dry test specimens as well as wet test specimens. The intention of this method is to simulate the deformation in the xy plane produced by the wearer of the absorbent article during normal use. All tests are performed in a room controlled at 23°C ± 3°C and 50% ± 2% relative humidity.

[0151] The bottom fixture consists of two cylindrical rods of polished stainless steel with a diameter of 3.175 mm and a length of 110 mm, each with frictionless roller bearings mounted on both ends. The two rods are mounted horizontally, aligned front to back and parallel to each other, with the top radius of the rods aligned vertically and free to rotate around the diameter of the cylinder through frictionless bearings. In addition, the fixture allows the two rods to move horizontally away from each other on the track so that a gap can be set between them while maintaining their orientation. The top fixture consists of a third cylindrical rod also made of polished stainless steel with a diameter of 3.175 mm and a length of 110 mm, with frictionless roller bearings mounted on both ends. When in position, the rods of the top fixture are parallel to and aligned front to back with the rods of the bottom fixture, and centered between the rods of the bottom fixture. Both fixtures include an integral adapter that is suitable for mounting in corresponding positions on a universal test frame and locking into position so that the rods are orthogonal to the movement of the test frame crossbar.

[0152] The gap between the bars of the lower fixture ("span") was set to 25 mm ± 0.5 mm (center of bar to center of bar), with the upper bar centered at the midpoint between the lower bars. The gauge length (bottom of the top bar to top of the lower bar) was set to 1.0 cm.

[0153] The thickness (thickness) ("caliper") of the test specimen is measured using a manually operated micrometer equipped with a pressure foot capable of applying a steady pressure of 0.1 psi ± 0.01 psi. The manually operated micrometer is a deadweight instrument that reads to the nearest 0.01 mm. A suitable instrument is a Mitutoyo series 543ID-C Digimatic, or equivalent, available from VWR International. The pressure foot is a flat, circular, movable surface not greater than 25.4 mm in diameter. The test specimen is supported by a horizontal, flat reference platform that is larger than and parallel to the surface of the pressure foot. The micrometer is zeroed against the horizontal, flat reference platform. The test specimen is placed on the platform, centered under the pressure foot. The pressure foot is lowered by hand at a rate of descent of 3 ± 1 mm / s until the full weight of the pressure is applied to the specimen. After 5 seconds have passed, the thickness is recorded as the caliper, to the nearest 0.01 mm.

[0154] Prepare the test fluid for metering the wet test specimens by adding 100.0 grams of sodium chloride (reagent grade, any convenient source) to 900 grams of deionized water in a 1 liter Erlenmeyer flask. Stir until the sodium chloride is completely dissolved.

[0155] Prior to testing, condition the absorbent article at 23°C ± 3°C and 50% ± 2% relative humidity for two hours. The dry test specimen is taken from a sample area free of any seams and creases or wrinkles, and is ideally taken from the center of the absorbent article (the intersection of the longitudinal and transverse centerlines). Prepare the dry specimen for MD (longitudinal) bending in the following manner: cut the dry specimen into a width of 50.8 mm along the CD (transverse; parallel to the transverse axis of the sample) and a length of 50.8 mm along the MD (parallel to the longitudinal axis of the sample), keep their orientation after cutting, and mark the surface facing the body (or the surface intended to face the finished body). Prepare the dry specimen for CD (longitudinal) bending in the following manner: cut the dry specimen into a width of 50.8 mm along the MD (transverse; parallel to the transverse axis of the sample) and a length of 50.8 mm along the CD (parallel to the longitudinal axis of the sample), keep their orientation after cutting, and mark the surface facing the body (or the surface intended to face the finished body). Measure the thickness of the test specimen as described herein and record it as the dry specimen thickness to the nearest 0.01 mm. Now measure the mass of the test specimen and record it as the dry mass to the nearest 0.001 gram. Calculate the mass (g) by dividing the area (0.002581 m 2 ) to calculate the basis weight of the sample and record it as the dry sample basis weight, accurate to 0.01 g / m 2 By changing the sample basis weight (g / m 2) divided by the sample thickness (mm), then divided the quotient by 1000 to calculate the bulk density of the sample and record it as the dry sample density to the nearest 0.01 g / cm 3 In a similar manner, five replicate dry test specimens were prepared.

[0156] The wet test specimen is initially prepared in exactly the same manner as the dry test specimen, and then the test fluid is added just before the test, as described below. First, the thickness and mass of the dry specimen are measured as described herein, and recorded as the initial thickness (accurate to 0.01mm) and the initial mass (accurate to 0.001g). Next, the dry specimen is completely immersed in the test fluid for 60 seconds. After 60 seconds have passed, the specimen is removed from the test fluid and vertically oriented for 30 seconds to allow any excess fluid to drip. As described herein, the thickness and mass of the wet specimen are now measured, and recorded as the wet specimen thickness (accurate to 0.01mm) and the wet specimen mass (accurate to 0.001g). If necessary, the mass of the test fluid in the test specimen is calculated by subtracting the initial mass (g) from the wet specimen mass (g) and recording it as the test specimen fluid amount (accurate to 0.001g). After removing the wet test specimen from the test fluid, it must be tested within 10 minutes. In a similar manner, five repeated wet test specimens were prepared.

[0157] The universal test frame for flexural bend testing was programmed to move the grips so that the top fixture moved downward relative to the lower fixture at a rate of 1.0 mm / s until the upper rod contacted the top surface of the specimen with a nominal force of 0.02 N and then continued for an additional 12 mm. The grips were then immediately returned to the original gauge length at a rate of 1.0 mm / s. Force (N) and displacement (mm) data were collected continuously at 100 Hz throughout the test.

[0158] Load the dry test specimen so that it spans the two bottom bars and is centered under the top bar with its sides parallel to the bars. For MD bending, the MD direction of the specimen is perpendicular to the length of the 3 bars. Start the test and continuously collect force and displacement data.

[0159] Plot force (N) versus displacement (mm). From the graph determine the maximum peak force and record it as the Dry MD Peak Load to the nearest 0.01 N. Now calculate the maximum slope of the curve between the initial force and the maximum force (during the loading portion of the curve) and record it to the nearest 0.1 unit. Calculate the modulus as follows and record it as the Dry MD Modulus to the nearest 0.001 N / mm 2 .

[0160] CD or MD dry or wet flexural modulus (N / mm 2 )=(slope×(span 3 )) / (4×sample width×(sample thickness 3 ))

[0161] Calculate the bending stiffness as follows and record it as dry MD bending stiffness to the nearest 0.1 N mm 2 .

[0162] CD or MD dry or wet bending stiffness (N mm 2 ) = modulus × moment of inertia

[0163] The moment of inertia (mm 4 )=(specimen width×(specimen thickness 3 )) / 12

[0164] In a similar manner, repeat the procedure for all five replicate dry test samples. The arithmetic mean between the five replicate dry test specimens is calculated for each of the parameters and reported as dry specimen "thickness" (accurate to 0.01 mm), dry specimen basis weight (accurate to 0.01 g / m 2 ), dry sample density (accurate to 0.001g / cm 3 ), dry CD or MD peak load (accurate to 0.01N), dry CD or MD flexural modulus (accurate to 0.001N / mm 2 ) and dry CD or MD bending stiffness (accurate to N mm 2 ).

[0165] The entire procedure is now repeated for all five replicates of the wet test specimens and the results are reported as wet CD or MD peak load (to the nearest 0.01 N), wet CD or MD flexural modulus (to the nearest 0.001 N / mm 2 ) and wet CD or MD bending stiffness (accurate to N mm 2 ).

[0166] Wet and dry CD ultra-sensitive 3-point bending method

[0167] The CD (cross direction) bending properties of the test specimens are measured using an ultra-sensitive 3-point bend test on a universal constant rate extension test frame (a suitable instrument is MTS Alliance using TestSuite software, available from MTS Systems Corp., Eden Prairie, MN, or its equivalent) equipped with a load cell suitable for measuring force. The test is performed on dry test specimens as well as wet test specimens. The intent of this method is to simulate the deformation in the xy plane produced by the wearer of the absorbent article during normal use. All tests are performed in a room controlled at 23°C ± 3°C and 50% ± 2% relative humidity.

[0168] The ultra-sensitive 3-point bend method is designed to maximize the force signal-to-noise ratio when testing materials with very low bending forces. The force signal is maximized by using a highly sensitive load cell (e.g. 5N), using a small span (the load is proportional to the cube of the span), and using a wide specimen width (the total load measured is proportional to the width). The fixture is designed so that the bend measurement is made under tension, allowing the fixture mass to be kept to a minimum. The noise in the force signal is minimized by keeping the load cell stationary to reduce mechanical vibration and inertial effects, and by keeping the mass of the fixture attached to the load cell as low as possible.

[0169] See also FIG. 11A to FIG. 11C , load sensor 1001 is mounted on the fixed clamp of the universal test frame. The ultra-sensitive fixture 1000 consists of three thin blades made of a lightweight rigid material (such as aluminum or equivalent). Each blade has a thickness of 1.0mm, rounded edges and a length that can accommodate a bending width of 100mm. Each of the blades has cavities 1004a and 1004b (outer blades) and 1005 (center blade), which are cut out to form blade material with a height h of 5mm along its horizontal edges. The two outer blades 1003a and 1003b are horizontally mounted to the movable clamp of the universal test frame, aligned parallel to each other, and their horizontal edges are vertically aligned. The span S between the two outer blades 1003a and 1003b is 5mm±0.1mm (inner edge to inner edge). The center blade 1002 is mounted to the load sensor on the fixed clamp of the universal test frame. When in position, the center blade 1002 is parallel to the two outer blades 1003a and 1003b and is centered at the midpoint between the outer blades 1003a and 1003b. The blade fixture includes integral adapters that are adapted to be mounted in corresponding locations on the universal test frame and locked into position so that the horizontal edge of the blade is orthogonal to the motion of the universal test frame crossbar.

[0170] Prepare the test fluid for metering the wet test specimens by adding 100.0 grams of sodium chloride (reagent grade, any convenient source) to 900 grams of deionized water in a 1 liter Erlenmeyer flask. Stir until the sodium chloride is completely dissolved.

[0171] Prior to testing, the samples were conditioned at 23°C ± 3°C and 50% ± 2% relative humidity for two hours. Dry test specimens were taken from sample areas where no seams and creases or wrinkles remained. Dry specimens were prepared for CD bending (i.e., bending perpendicular to the transverse axis of the sample) in the following manner: the dry specimens were cut into a width of 50.0 mm along the CD (transverse; parallel to the transverse axis of the sample) and a length of 100.0 mm along the MD (longitudinal; parallel to the longitudinal axis of the sample), maintaining their orientation after cutting, and marking the body-facing surface (or the surface intended to face the finished body). In a similar manner, five repeated dry test specimens were prepared.

[0172] The wet test specimens were initially prepared in exactly the same manner as the dry test specimens, followed by the addition of the test fluid just prior to testing, as described below. The dry specimens were completely immersed in the test fluid for 60 seconds. After the 60 seconds had elapsed, the specimens were removed from the test fluid and oriented vertically for 30 seconds to allow any excess fluid to drip off. After the wet test specimens were removed from the test fluid, the test must be performed within 10 minutes. In a similar manner, five replicate wet test specimens were prepared.

[0173] The universal test frame was programmed so that the movable chuck was set to move in a direction opposite to the fixed chuck at a rate of 1.0 mm / s. The chuck movement began with the specimen 1006 lying flat on the outer blades 1003a and 1003b and not deflected, continued as the inner horizontal edge of the cavity 1005 in the center blade 1002 contacted the top surface of the specimen 1006, and further continued with an additional 4 mm of chuck movement. The chuck stopped at 4 mm and then immediately returned to zero at a rate of 1.0 mm / s. Force (N) and displacement (mm) were collected at 50 Hz throughout the process.

[0174] Prior to loading the test specimen 1006, the outer vanes 1003a and 1003b are moved toward the center vane 1002 and then past the center vane until a gap C of approximately 3 mm exists between the inner horizontal edges of the cavities 1004a and 1004b in the outer vanes 1003a and 1003b and the inner horizontal edge of the cavity 1005 in the center vane 1002 (see Fig. 11C). Sample 1006 is placed in gap C so that it spans the inner horizontal edges of cavities 1004a and 1004b in outer leaves 1003a and 1003b, oriented so that the MD (short edge) of the sample is perpendicular to the horizontal edges of the leaves and the body-facing surface of the sample faces upward. Center sample 1006 between outer leaves 1003a and 1003b. Slowly move outer leaves 1003a and 1003b in a direction opposite to the fixed chuck until the inner horizontal edge of cavity 1005 in center leaf 1002 contacts the top surface of sample 1006. Start testing and continuously collect force and displacement data.

[0175] Force (N) versus displacement (mm) is plotted. The maximum peak force is recorded to the nearest 0.001 N. The area under the curve from the start of loading until the maximum peak force is calculated and recorded as the bending energy to the nearest 0.001 N-mm. The recovery energy is calculated as the area under the curve where the force is unloaded from the maximum peak to 0.0 N, and the recovery energy is recorded to the nearest 0.001 N-mm. In a similar manner, the entire test sequence is repeated for a total of five dry test specimens and five wet test specimens.

[0176] For each test specimen type (dry and wet), calculate the arithmetic mean of the maximum peak force among similar specimens to the nearest 0.001 N and report as Dry Peak Load and Wet Peak Load, respectively. For each test specimen type (dry and wet), calculate the arithmetic mean of the bending energy among similar specimens to the nearest 0.001 N-mm and report as Dry Bend Energy and Wet Bend Energy, respectively. For each test specimen type (dry and wet), calculate the arithmetic mean of the recovery energy among similar specimens to the nearest 0.001 N-mm and report as Dry Recovery Energy and Wet Recovery Energy, respectively.

[0177] Wet and dry push-up compression methods

[0178] The Gathered Compression Test Method measures the force-to-displacement behavior of an intentionally "gathered" absorbent article test sample over five cycles of load application ("compression") and load removal ("recovery") using a universal constant-rate extension test frame equipped with a load cell (a suitable instrument is MTS Alliance using TestSuite software, available from MTS Systems Corp., Eden Prairie, MN, or its equivalent), the forces measured being within 1% to 99% of the limits of the load cell. The test is conducted on dry test specimens as well as wet test specimens metered with a specified amount of test fluid. The intent of this method is to simulate the deformations produced in the z-plane of the crotch region of an absorbent article or component thereof when worn by a wearer during sit-stand exercise. All tests are conducted in a room controlled at 23°C ± 3°C and 50% ± 2% relative humidity.

[0179] Test equipment in Figures 12 to 13B Depicted in . The bottom fixed fixture 3000 consists of two matching sample clamps 3001, each clamp is 100mm wide, each clamp is mounted on its own movable platform 3002a, 3002b. The clamps have a 110mm long "blade" 3009, which rests against a 1mm thick hard rubber surface 3008. When closed, the clamps are flush with the inside of their corresponding platforms. The clamps are aligned so that they hold the unassembled specimens horizontally and orthogonal to the pulling axis of the tensile tester. The platforms are mounted on guide rails 3003, which allow them to be moved horizontally from left to right and locked in place. The guide rails have adapters 3004 compatible with the brackets of the tensile tester, which can fix the platforms horizontally and orthogonally to the pulling axis of the tensile tester. The upper fixture 2000 is a cylindrical plunger 2001, which has an overall length of 70mm and a diameter of 25.0mm. The contact surface 2002 is flat, without curvature. The plunger 2001 has an adapter 2003 compatible with the bracket of the load cell, which enables the plunger to be fixed orthogonally to the pulling axis of the tensile tester.

[0180] Before testing, the test sample is conditioned at 23°C ± 3°C and 50% ± 2% relative humidity for at least 2 hours. Prepare the test specimen as follows. When testing a complete absorbent article, remove the release paper (if present) from any panty adhesive on the garment-facing side of the article. Apply talcum powder lightly to the adhesive to relieve any stickiness. If there is a hoop, cut them off with scissors so as not to interfere with the top sheet or any other underlying layer of the article. The article is placed on a workbench in a manner facing the body surface upward. Mark the intersection of the longitudinal centerline and the transverse centerline on the article. Use a rectangular punching die or equivalent cutting device to cut out a sample of 100mm in the longitudinal direction by 80mm in the transverse direction, with its center located at the intersection of the centerline. When testing the material layer or layered component of the absorbent article, place the material layer or layered component on the workbench and orient it to be integrated into the finished product, that is, identify the surface facing the body and the transverse and longitudinal axes. Use a rectangular punching die or equivalent cutting device to cut out a sample of 100mm in the longitudinal direction by 80mm in the transverse direction, with its center located at the intersection of the centerline. Measure the mass of the sample and record it to the nearest 0.001 gram. Divide the mass (g) by the area (0.008 m 2 ) to calculate the basis weight of the sample and record it as basis weight, accurate to 1g / m 2 .

[0181] The specimens can be analyzed both wet and dry. No further preparation is required for dry specimens. Prepare the test fluid for metering the wet test specimens by adding 100.0 grams of sodium chloride (reagent grade, any convenient source) to 900 grams of deionized water in a 1 liter conical flask. Stir until the sodium chloride is completely dissolved. A total of 7 ml of test solution is metered into the wet specimens as detailed below.

[0182] A calibrated Eppendorf-type pipette was used to add the liquid dose, spreading the fluid over the entire body-facing surface of the specimen over a period of approximately 3 seconds. The wet specimen was tested 10.0 min ± 0.1 min after the dose was applied.

[0183] The tensile tester is programmed to zero the load cell and then lower the upper clamp at a rate of 2.00 mm / sec until the contact surface of the plunger contacts the specimen and the reading at the load cell is 0.02 N. Zero the chuck. The system is programmed to lower the chuck by 15.00 mm at a rate of 2.00 mm / sec and then immediately raise the chuck by 15.00 mm at a rate of 2.00 mm / sec. Repeat this cycle for a total of five cycles with no delay between cycles. Data is collected at a frequency of 50 Hz during all compression / decompression cycles.

[0184] Position the left platform 3002a 2.5 mm (distance 3005) from the side of the upper plunger. Lock the left platform in place. This platform 3002a will remain fixed throughout the experiment. Align the right platform 3002b 50.0 mm (distance 3006) from the fixed clamp. Raise the upper probe 2001 so that it will not interfere with the loading of the specimen. Open both clamps 3001. See Fig.13A , place the dry specimen in the fixture with its longitudinal edge (i.e., the 100 mm long edge). With the dry specimen centered transversely, securely fasten both edges in the fixture. Fig. 13B , move the right platform 3002b towards the fixed platform 3002a by a distance of 20 mm so that a spacing of 30.0 mm is achieved between the left and right clamps. When positioning the movable platform, allow the dry specimen to bend upward. Now manually lower the probe 2001 until the bottom surface is approximately 1 cm above the top of the bent specimen.

[0185] The test was started and force (N) versus displacement (mm) data was continuously collected for all five cycles. A graph of force (N) versus displacement (mm) was plotted separately for all cycles. A representative curve is shown in Fig.14AFrom this curve, determine the dry maximum compressive force for each cycle to the nearest 0.01 N, then multiply by 101.97 and record to the nearest 1 gram-force. Calculate the "% Dry Recovery" between the "First Cycle" and the "Second Cycle" as (TD-E2) / (TD-E1)*100 and record to the nearest 0.01%, where TD is the total displacement and E2 is the elongation on the second compression curve that exceeds 0.02 N. In a similar manner, calculate the % Dry Recovery between the first cycle and the additional cycles as (TD-E1) / (TD-E1)*100 and record to the nearest 0.01%. See Fig. 14B , the dry compression energy of cycle 1 is calculated as the area under the compression curve (i.e., Area A+B) and recorded to the nearest 0.1 N-mm. The dry energy loss of cycle 1 is calculated as the area between the compression and decompression curves (i.e., Area A) and recorded to the nearest 0.1 N-mm. The dry recovery energy of cycle 1 is calculated as the area under the decompression curve (i.e., Area B) and reported to the nearest 0.1 N-mm. The dry compression energy (N-mm), dry energy loss (N-mm), and dry recovery energy (N-mm) of each of the other cycles are calculated in a similar manner and recorded to the nearest 0.1 N-mm. In a similar manner, a total of five repeated dry test specimens are analyzed, and the arithmetic mean between the five dry repeats of each parameter (including basis weight) as described above is reported.

[0186] Now repeat the entire procedure for a total of five replicate wet test specimens, reporting the results for each of the five cycles as the arithmetic mean of the five wet replicates for the following: Wet Maximum Compressive Force (to the nearest 1 gram-force) per cycle, Wet Compressive Energy (to the nearest 0.1 N-mm) per cycle, Wet Energy Loss (to the nearest 0.1 N-mm) per cycle, Wet Recovery Energy (to the nearest 0.1 N-mm) per cycle, and Wet Recovery % per cycle. Of particular importance are the Fifth Cycle Wet Recovery Energy and Fifth Cycle Wet Recovery % properties from this test method.

[0187] CD cyclic elongation to 3% strain

[0188] Cyclic stretch and recovery response of absorbent article specimens is measured using a universal constant rate extension test frame for ten cycles of sustained load application ("elongation") and load removal ("recovery"). The test specimen is cycled ten times to 3% engineering strain and then returned to zero engineering strain. For each cycle, stiffness, peak load, normalized peak energy, normalized recovery energy, strain at the beginning of the cycle, and strain at the end of the cycle (i.e., "permanent strain") are calculated and reported. The intent of this method is to understand the ability of a sample to stretch in the xy plane due to body forces and then return to its original state. All measurements are performed in a laboratory maintained at 23°C ± 2°C and 50% ± 2% relative humidity, and the specimens are conditioned in this environment for at least 2 hours prior to testing.

[0189] A suitable universal constant rate extension test frame is an MTS Alliance interfaced with a computer running TestSuite control software (available from MTS Systems Corp, Eden Prairie, MN), or equivalent. The universal test frame is equipped with a load cell, the forces measured being within 1% to 99% of the load cell's limit. The fixtures used to grip the test specimens are lightweight (<80 grams), vise-action fixtures with knife or serrated edge gripping faces at least 40 mm wide. The fixtures are mounted on the universal test frame and are mounted so that they are horizontally and vertically aligned with each other.

[0190] The test specimens are prepared as follows. If necessary, the test material is obtained by cutting the test material from the absorbent article. When cutting the test material, no contamination or deformation of the material layer is caused during the process. The test specimen is cut from an area of ​​the test material without any residual creases or wrinkles. The test specimen is as long as the transverse length of the article (parallel to the transverse axis of the article, or the intended transverse axis of the article). When cutting specimens from absorbent articles of different sizes and widths, the total specimen length (L 总计 ) may vary from product to product, so the results will be normalized to compensate for this variation. The test specimen has a width of 25.4 mm (parallel to the longitudinal axis or intended longitudinal axis of the article). Specimen width (w) = 25.4 mm. Measure and record the total specimen length (L 总计 ), accurate to 0.1 mm. In a similar manner, five repeated test specimens were prepared.

[0191] The thickness (t) of the test specimen is measured using a manually operated micrometer equipped with a pressure foot capable of applying a steady pressure of 0.1psi ± 0.01psi. The manually operated micrometer is a static heavy instrument with a reading accurate to 0.01mm. A suitable instrument is a Mitutoyo series 543ID-C Digimatic purchased from VWR International, or an equivalent. The pressure foot is a flat circular movable surface with a diameter not greater than 25.4mm. The test specimen is supported by a horizontal flat reference platform that is larger than and parallel to the surface of the pressure foot. The micrometer is zeroed for the horizontal flat reference platform. The test specimen is placed on the platform, centered below the pressure foot. The pressure foot is lowered by hand at a rate of descent of 3 ± 1mm / s until the full weight of the pressure is applied to the specimen. After 5 seconds have passed, the thickness is recorded as the specimen thickness (t), accurate to 0.01mm.

[0192] Prepare the universal test frame as follows. Set the initial grip-to-grip separation distance to a nominal gauge length (L) that is shorter than the total specimen length. 标称 ) and allows the specimen to be securely clamped at both ends (i.e., L 标称 <L 总计 ). The grips are then zeroed. The test frame is programmed to move the grips closer together with an intentional slack of 1 mm to ensure that no pre-tension is present on the test specimen at the start of the test. (During this movement, the specimen will become relaxed between the tension grips.) Next, the grips will move apart at a relaxation rate of 1 mm / s until a relaxation preload of 0.05 N is exceeded. At this point, the following holds. 1) The grip position signal (mm) is defined as the specimen relaxation (L 松弛 ). 2) Calculate the initial specimen gauge length (L0) as the nominal gauge length plus the relaxation L0 = L 标称 +L 松弛 , where the units are in millimeters. 3) The clamp extension (ΔL) is set to zero (0.0mm). 4) The clamp displacement (mm) is set to zero (0.0mm). At this position, the engineering strain is zero, 0.0. Engineering strain is calculated as the change in length (ΔL) divided by the initial length (L0). Engineering strain = ΔL / L0. For one test cycle, the clamps are moved apart at an initial speed of 1mm / s until the engineering strain endpoint of 0.03mm / mm is exceeded, followed by the clamps moving toward each other at an initial speed of 1mm / s until the clamp signal becomes less than the clamp return position of 0mm. This test cycle is repeated until a total of 10 cycles are completed.

[0193] The test was performed by inserting the test specimen into the grips so that the long axis of the specimen was parallel and centered with the movement of the grips. The test was started and time, force and displacement data were continuously collected at a data acquisition rate of 100 Hz.

[0194] For all ten cycles, plot force (N) versus displacement (mm). For each cycle, do the following. Record the peak load to the nearest 0.01N. Calculate the peak energy (E 峰值 ), as the area under the load versus displacement curve from the start of the cycle to the strain endpoint of 0.03 mm / mm (during the loading portion of the cycle), and recorded to the nearest 0.01 N*mm. Calculate the return energy (E 返回 ) is taken as the area under the load versus displacement curve from the strain endpoint of 0.03 mm / mm to the chuck return of 0 mm (during the unloading portion of the cycle) and is recorded as the recovery energy to the nearest 0.01 N*mm. The normalized peak energy (NE 峰值 ) is calculated as the peak energy divided by the initial length, where NE 峰值 =E 峰值 / L0 and record it to the nearest 0.01mN. 返回 ) is calculated as the returned energy divided by the initial length (NE 返回 =E 返回 / L0) and record it to the nearest 0.01mN. 峰值 and NE 返回 The unit is millinewton (mN).

[0195] Now plot the engineering stress (σ) versus engineering strain for all ten cycles and for each cycle do the following. 2 Engineering stress in units is the load divided by the cross-sectional area of ​​the specimen, where the cross-sectional area is the specimen width (w) multiplied by the thickness (t), σ = load / (w * t). The modulus or the slope of the stress-strain curve is determined for the line between the point occurring at the minimum force and the point occurring at the maximum force (during the loading portion of the cycle) and recorded as the modulus, accurate to 0.01 N / mm. Stiffness is calculated by multiplying the modulus by the specimen thickness and recorded as tensile stiffness, accurate to 0.01 N / mm. The strain of the test specimen at the beginning of the cycle is defined as the strain when the cycle exceeds a relaxed preload of 0.05 N (during the loading portion of the cycle) and is recorded as the initial strain of the cycle, accurate to 0.01 mm / mm. The strain of the test specimen at the end of the cycle is defined as the strain when the load becomes less than the preload of 0.05 N of the cycle (during the unloading portion of the cycle) and is recorded as the permanent strain, accurate to 0.01 mm / mm. In a similar manner, the entire procedure is now repeated for all five repetitions.

[0196] For each of the ten cycles, the arithmetic mean of the five replicate test specimens is calculated for each of the parameters and reported as peak load (accurate to 0.01N), normalized peak energy (accurate to 0.01mN), normalized recovery energy (accurate to 0.01mN), tensile stiffness (accurate to 0.01N / mm), cycle initial strain (accurate to 0.01mm / mm) and permanent strain (accurate to 0.01mm / mm).

[0197] Method for measuring pattern spacing and area of ​​structural bonding areas

[0198] On the image of the absorbent article sample collected using a flatbed scanner, the spacing between the discrete structural bonding sites used to produce a quilted pattern on the absorbent article sample, and the total area occupied by the sum of these elements in the specified area of ​​the sample are measured. The scanner can scan in reflective mode with a resolution of 2400dpi and 8-bit grayscale. A suitable scanner is an Epson Perfection V750 Pro from Epson America Inc., Long Beach CA, or an equivalent. The scanner interacts with a computer running an image analysis program. A suitable program is ImageJ v.1.52, National Institute of Health, USA, or an equivalent. The sample image is distance calibrated according to the image collected by the NIST-verified straight ruler. In order to achieve maximum contrast, the sample is backed with an opaque black background of uniform color before the image is collected. All tests are carried out in a conditioning room maintained at about 23 ± 2°C and about 50 ± 2% relative humidity.

[0199] Each test sample is prepared as follows. The absorbent article is removed from any wrapping paper present. If the article is folded, it is gently unfolded and any wrinkles are smoothed. If wings are present, they are extended but the release paper remains intact. Prior to testing, the test samples are conditioned for 2 hours at about 23°C ± 2°C and about 50% ± 2% relative humidity.

[0200] The image is obtained as follows. A ruler is placed on the scanning bed so that it is oriented parallel to the side of the scanner glass. An image of the ruler (calibration image) is collected in reflection mode at a resolution of 2400dpi (approximately 94 pixels / mm) and 8-bit grayscale. The calibration image is saved as an uncompressed TIFF format file. After obtaining the calibration image, the ruler is removed from the scanner glass and the test sample is scanned as follows under the same scanning conditions. The test sample is placed on the center of the scanner glass and fixed, if necessary, so that it lies flat, wherein the body-facing surface of the sample faces the glass surface of the scanner. The sample is oriented in a manner that the entire sample is within the glass surface. A black background is placed on top of the sample, the scanner lid is closed, and a scanned image of the entire sample is collected with the same settings as those used for the calibration image. The sample image is saved as an uncompressed TIFF format file.

[0201] Analyze the test sample image as follows. Open the calibration image file in the image analysis program and calibrate the image resolution using an imaging ruler to determine the number of pixels per millimeter. Now open the sample image in the image analysis program and set the distance scale using the image resolution determined from the calibration image. Now visually inspect the pattern of embossed elements present on the sample in the image and identify the pattern area to be analyzed. For example, the absorbent article can be divided into three zones of equal length in the longitudinal direction, such as the front third (Zone 1), the center third (Zone 2), and the end third (Zone 3). Use the image analysis tool to draw a shape along the outer perimeter of the first discrete area to be analyzed. Measure the area of ​​this first area and record it as the total area of ​​Zone 1 to the nearest 0.01mm 2 . Now measure the area of ​​each individual, discrete embossed element located inside the perimeter of Zone 1 as follows. Draw a minimum bounding circle around the individual embossed element so that no part of the embossed element lies outside the bounding circle. Now measure the area of ​​the bounding circle for that embossed element and record the embossed element area to the nearest 0.01 mm 2 In a similar manner, measure the area of ​​each embossed element, including the portion of the embossed element that is within Zone 1, and record each to the nearest 0.01 mm. 2 Now add up the areas of all embossed elements in zone 1 and record this as the total embossed element area for zone 1 to the nearest 0.01 mm. 2. Divide the total embossed element area of ​​Zone 1 by the total area of ​​Zone 1, then multiply by 100 and record as the % of the total area of ​​Zone 1 occupied by the embossed elements. The spacing between each discrete embossed element within Zone 1 is measured as follows. As described herein, measure the distance from the center of the smallest bounding circle drawn around the discrete embossed elements within Zone 1 to the center of the smallest bounding circle drawn around the nearest adjacent discrete embossed element within Zone 1 and record that distance as the embossed spacing, accurate to 0.01 mm. Repeat in a similar manner for all adjacent embossed elements within Zone 1 and record each distance, accurate to 0.01 mm. Now calculate the arithmetic mean between all measured embossing spacings measured between the nearest neighbors within Zone 1 and record as the Zone 1 embossing spacing, accurate to 0.01 mm.

[0202] In a similar manner, the entire procedure is repeated for each additional zone containing embossed elements present on the test sample and labeled accordingly as Zone 2, Zone 3, etc.

[0203] Light touch rewetting

[0204] The touch rewet method is a method of quantitatively measuring the mass of liquid that flows from an absorbent article test sample when a weight is applied for a specified length of time, to which a specified volume of artificial menstrual fluid (AMF; as described herein) has been metered. All measurements are performed in a laboratory maintained at 23°C ± 2°C and 50% ± 2% relative humidity.

[0205] Use a syringe pump equipped with a disposable syringe to meter the test sample. A suitable pump is Compact S (available from B. Braun) or equivalent, and must be able to accurately dispense AMF at a rate of 42 ml / min. A disposable syringe of sufficient volume (e.g., BD Plastipak 20 mL) connected to a flexible tube with an inner diameter of 3 / 16" (e.g., Original Tubing, purchased from Brau, or equivalent). AMF was prepared as described herein and allowed to reach room temperature (23°C ± 2°C) before being used in the test. Before starting the measurement, the syringe was filled with AMF and the flexible tube was primed with liquid, and the dispensing rate (42 ml / min) and metering volume (4.0 mL ± 0.05 mL) were verified according to the manufacturer's instructions. The flexible tube was then installed so that it was oriented vertically above the test sample, and the distance between the tip of the tube and the test sample surface was 19 mm. Note that the AMF must be removed from the syringe every 15 minutes and mixed thoroughly.

[0206] The rewetting weight assembly consists of an acrylic plate and a stainless steel weight. The acrylic plate has dimensions of 65 mm x 80 mm and a thickness of approximately 5 mm. The stainless steel weight together with the acrylic plate has a combined mass of 2 pounds (907.19 g) to apply a pressure of 0.25 psi below the surface of the acrylic plate.

[0207] For each test sample, five pieces of filter paper measuring 4 inches by 4 inches were used as the rewetting substrate. Prior to testing, the filter paper was conditioned at 23°C ± 2°C and 50% ± 2% relative humidity for at least 2 hours. Suitable filter paper has a basis weight of about 139 gsm, a thickness of about 700 microns, has an absorption rate of about 1.7 seconds, and is available from Ahlstrom-Munksjo North America LLC, Alpharetta, GA VWR International as Ahlstrom grade 989 or equivalent.

[0208] Prepare the test samples according to the following steps. Before testing, condition the test samples at 23°C ± 2°C and 50% ± 2% relative humidity for at least 2 hours. Remove the test samples from all packaging, being careful not to press or pull the product when handling. Place the test sample on a horizontal rigid flat surface and gently flatten any creases. Determine the test position as follows. For symmetrical samples (i.e., when the midpoint of the longitudinal axis of the sample is divided laterally, the front of the sample has the same shape and size as the back of the sample), the test position is the intersection of the midpoint of the longitudinal axis of the sample and the midpoint of the transverse axis. For asymmetrical samples (i.e., when the midpoint of the longitudinal axis of the sample is divided laterally, the front of the sample does not have the same shape and size as the back of the sample), the test position is the midpoint of the longitudinal axis of the sample and the intersection of the transverse axis located at the midpoint of the sample wing. Prepare a total of three test samples.

[0209] The test sample is placed on a horizontal flat rigid surface, where the previously identified test position is centered directly below the tip of the flexible tube. The height of the tube is adjusted so that it is 19.0mm above the test sample surface. The pump is started to dispense 4.0mL ± 0.05mL of AMF at a rate of 42ml / min. Once the AMF is fully dispensed, a 10-minute timer is started. The mass of 5 filter papers is now obtained and recorded as dry mass, accurate to 0.001 grams. When 10 minutes have passed, five pre-weighed filter papers are placed on the test sample, and the stack is centered on the metering position. Now an acrylic plate is placed in the center of the top of the filter paper so that the long side of the plate is parallel to the longitudinal axis of the test sample. Now carefully lower the stainless steel weight centered above the acrylic plate and immediately start the timer for 30 seconds. After 30 seconds have passed, gently remove the rewetting weight and acrylic plate and set aside. The mass of five filter papers is obtained and recorded as wet mass, accurate to 0.001 grams. Subtract the dry mass from the wet mass of the filter paper and record as the rewet to the nearest 0.001 gram. Before testing the next sample, wipe off any residual test liquid from the underside of the acrylic plate. Repeat in a similar manner for a total of three replicate test samples.

[0210] The arithmetic mean of the rewet among the three replicate test samples was calculated and reported as "Light Touch Rewet" to the nearest 0.001 g.

[0211] Artificial menstrual fluid (AMF) preparation

[0212] Artificial menstrual fluid (AMF) consists of a mixture of defibrillated sheep blood, phosphate buffered saline solution and a mucus component. AMF is prepared so that it has a viscosity between 7.15 and 8.65 centistokes at 23°C.

[0213] The viscosity of AMF is measured using a low viscosity rotational viscometer (a suitable instrument is a Cannon LV-2020 rotational viscometer with a UL adapter from Cannon Instrument Co., State College, PA, or an equivalent instrument). A spindle of appropriate size within the viscosity range is selected, and the instrument is operated and calibrated according to the manufacturer. The measurement is performed at 23°C ± 1°C and at 60rpm. Results are reported to the nearest 0.01 centistoke.

[0214] The reagents required for AMF preparation include: defibrinated sheep blood with a packed cell volume of 38% or greater (collected under sterile conditions and purchased from Cleveland Scientific, Inc., Bath, OH, or equivalent), gastric mucin with a viscosity of 3-4 centistokes when prepared as a 2% aqueous solution (crude form, sterile, purchased from American Laboratories, Inc., Omaha, NE, or equivalent), 10% v / v lactic acid in water, 10% w / v potassium hydroxide in water, disodium hydrogen phosphate (reagent grade), sodium chloride (reagent grade), sodium dihydrogen phosphate (reagent grade), and distilled water, each purchased from VWR International or equivalent source.

[0215] Phosphate buffered saline solution consists of two separately prepared solutions (Solution A and Solution B). To prepare 1 L of Solution A, add 1.38 ± 0.005 g of monobasic sodium phosphate and 8.50 ± 0.005 g of sodium chloride to a 1000 mL volumetric flask and add distilled water to the flask. Mix thoroughly. To prepare 1 L of Solution B, add 1.42 ± 0.005 g of disodium hydrogen phosphate and 8.50 ± 0.005 g of sodium chloride to a 1000 mL volumetric flask and add distilled water to the flask. Mix thoroughly. To prepare phosphate buffered saline solution, add 450 ± 10 mL of Solution B to a 1000 mL beaker and stir at low speed on a stir plate. Insert a calibrated pH probe (accurate to 0.1) into the beaker of Solution B and add enough Solution A while stirring to bring the pH to 7.2 ± 0.1.

[0216] The mucus component is a mixture of phosphate buffered saline solution, potassium hydroxide aqueous solution, gastric mucin and lactic acid aqueous solution. The amount of gastric mucin added to the mucus component directly affects the final viscosity of the prepared AMF. In order to determine the amount of gastric mucin required to obtain AMF in the target viscosity range (7.15-8.65 centistokes at 23°C), 3 batches of AMF with different amounts of gastric mucin were prepared in the mucus component, and then the exact amount required was interpolated from the concentration-viscosity curve using a three-point least squares linear fit. The successful range of gastric mucin is usually between 38 grams and 50 grams.

[0217] To prepare approximately 500 mL of the mucus fraction, 460 ± 10 mL of the previously prepared phosphate buffered saline solution and 7.5 ± 0.5 mL of a 10% w / v potassium hydroxide aqueous solution were added to a 1000 mL heavy glass beaker. The beaker was placed on a stirring hot plate and the temperature was raised to 45°C ± 5°C while stirring. A predetermined amount of gastric mucin (± 0.50 g) was weighed and slowly sprinkled into the previously prepared liquid that had reached 45°C without agglomeration. The beaker was covered and mixing continued. Within 15 minutes, the temperature of the mixture was brought to above 50°C, but not exceeding 80°C. While maintaining this temperature range, heating was continued for 2.5 hours with gentle stirring. After 2.5 hours, the beaker was removed from the hot plate and cooled to below 40°C. Next, 1.8 ± 0.2 mL of a 10% v / v lactic acid aqueous solution was added and mixed thoroughly. The mucus fraction mixture was autoclaved at 121°C for 15 minutes and cooled for 5 minutes. The mixture of mucus components was taken out from the autoclave and stirred until the temperature reached 23°C ± 1°C.

[0218] Allow the temperature of the sheep blood and mucus components to reach 23°C ± 1°C. Using a 500 mL graduated cylinder, measure the volume of the entire batch of previously prepared mucus components and add it to a 1200 mL beaker. Add an equal amount of sheep blood to the beaker and mix thoroughly. Using the viscosity method described above, ensure that the viscosity of the AMF is between 7.15-8.65 centistokes. If not, dispose of the batch and make another batch as needed for adjusting the mucus component.

[0219] Unless intended for immediate use, qualified AMF should be refrigerated at 4°C. After preparation, AMF may be stored in an airtight container at 4°C for up to 48 hours. Prior to testing, the AMF must be brought to 23°C ± 1°C. After testing is complete, discard any unused portion.

[0220] Flex Bond Channel Measurement

[0221] The flexure bonding embossing length, the flexure bonding landing area length, the flexure bonding channel width and the flexure bonding channel depth of the flexure bonding channel area formed near the central part of the absorbent article test sample are measured using optical profilometry to obtain the regional surface topography of the body-facing side of the test sample. The flexure bonding embossing length, the flexure bonding landing area length and the flexure bonding channel width of the flexure bonding channel are measured at the base of the depression, and the depth of the flexure bonding channel is measured relative to the adjacent non-channelized area. In addition, the bending properties of the test specimens in the prepared flexure bonding channel area are measured on a universal constant speed extension test frame. All tests are carried out in a room controlled at 23°C ± 3°C and 50% ± 2% relative humidity, and the test samples and specimens are conditioned in this environment for at least 2 hours before testing.

[0222] For the flex bond embossing length, length of the landing area between the flex bond embossings, channel width and channel depth methods, an optical 3D surface topography measurement system is used to record a three-dimensional (3D) surface topography image of the body-facing side of the test sample. A suitable optical 3D surface topography measurement system is a MikroCAD Premium instrument commercially available from LMI Technologies Inc. of Vancouver, Canada, or an equivalent. The system includes the following main components: a) a digital light processing (DLP) projector with direct digital control of micromirrors; b) a CCD camera with a resolution of at least 1600x1200 pixels; c) projection optics suitable for measuring an area of ​​at least 140mm×105mm; d) recording optics suitable for measuring an area of ​​140mm×105mm; e) a table tripod based on a small hard stone board; f) a blue LED light source; g) a measurement, control and evaluation computer running surface texture analysis software (suitable software is a CCD camera with a resolution of at least 1600x1200 pixels); c) a CCD camera with a resolution of at least 1600x1200 pixels; c) a CCD camera with a resolution of at least 1600x1200 pixels; d ... Technology's MikroCAD software or equivalent); and h) calibration plates purchased from suppliers for lateral (XY) and vertical (Z) calibration. The optical 3D surface topography measurement system uses digital micromirror pattern edge projection technology to measure the surface height of the sample. The measurement result is a 3D image of the surface height (defined as the Z axis) relative to the displacement in the horizontal (XY) plane. The system has a field of view of 140×105 mm with an XY pixel resolution of approximately 85 microns. The height resolution is set to 0.5 microns / count and the height range is + / -10 mm. Prior to testing, the instrument was calibrated according to the manufacturer's instructions using calibration plates available from the supplier for lateral (XY plane) and vertical (Z axis).

[0223] Prepare the absorbent article test sample for surface topography measurement and subsequent channel MD bending resistance measurement as follows. If necessary, unfold the absorbent article, but keep the protective cover on the panty adhesive (i.e. wrapping paper or release paper) in place. Identify and mark the front and rear of the article. In addition, identify and mark the left and right sides of the article relative to the left and right sides of the wearer. If the article was previously folded, use scissors or equivalent sharp cutting devices to cut along the width of the article at the position of about 1cm inside and parallel to the front fold line, so that any residue of the folded or creased material is removed and discarded from the front of the article. In a similar manner, cut along the width of the article at the position of about 1cm inside and parallel to the rear fold line, to remove and discard any residue of the folded or creased material from the rear of the article. After cutting, the remaining center portion of the absorbent article is retained as a test sample of about 60mm but not less than 40mm in length. As the residue of the folded material is removed, the test sample will be laid flat on a horizontal rigid surface. The protective cover is now removed from the female panty adhesive and a light dusting of talcum powder is applied to the adhesive to relieve tack. In a similar manner, a total of five replicate test samples are prepared.

[0224] Obtain the 3D surface topography image of the test sample as follows.The test sample is transferred to the MikroCAD (or equivalent) stage below the camera.The test sample is oriented so that the longitudinal axis of the left and right flexure bonding channel areas is perpendicular to the major axis (X-axis) of the instrument field of view.According to the measurement procedure recommended by the instrument manufacturer, the 3D surface topography image of the test sample is collected, which may include focusing the measurement system and performing brightness adjustment.Pre-filtering option is not used.The height image file collected is saved to the evaluation computer running the surface texture analysis software.

[0225] The 3D surface topography image was opened in the surface texture analysis software. The following filtering processes were then performed on the image: 1) invalid points were removed; 2) 3×3 pixel median filtering was used to remove noise; and 3) 3×3 pixel mean filtering was used to smooth the surface.

[0226] Flex Bond Embossing Length Method:

[0227] To measure the flex bond embossing length "L", a two-dimensional (2D) line profile (a sub-sampling of the 3D surface image) is extracted from a position within one of the individual recessed areas within the flex bond channel region perpendicular to the short side of the recess (i.e., the line crosses the longitudinal axis of the recess). The line profile extends across the entire length of the individual channel recess along its central longitudinal axis and includes non-recessed areas directly adjacent to both ends of the channel. Those skilled in the art will appreciate that if the resulting line profile does not generally represent the approximate profile of the flex bond channel region due to measurement noise or the presence of localized wrinkling or deformed channels (i.e., channels having a depth of less than 1 mm as determined by the flex bond channel depth method described herein), another test position at the individual recessed area of ​​the flex bond channel should be measured so that such artifacts are not present. A height profile of the line is now created (height (mm) vs. line length (mm)). It will be apparent to those skilled in the art that the flex bond channel region (minimum Z value) and the non-channel region (maximum Z value adjacent to the channel) are located on the height profile, such as Fig.15 Depicted. This line profile depicts an exemplary length of a recessed area in a flexure bonding channel. Determine the minimum height value (y-axis) on the line profile. Now move from the minimum height value to a position 100 microns away from the minimum height value in the z direction (y-axis) along the line on the left side of the profile, and set a "left" mark on the line profile. In a similar manner, move from the minimum height value to a position 100 microns away from the minimum height value in the z direction (y-axis) along the line on the right side of the profile, and set a "right" mark on the line profile. Measure the horizontal x distance between the left and right marks placed on the line profile, and record it as the flexure bonding channel length, accurate to 0.1mm. Now repeat the whole process until a total of five separate recessed areas of the flexure bonding channel have been analyzed on the test sample. In a similar manner, measure a total of five separate recessed areas of the flexure bonding channel on each of the remaining four repeated test samples. Now calculate the arithmetic mean of all the flexure bonding channel length values ​​repeatedly recorded across all five test samples, and report it as flexure bonding embossing length "L", accurate to 0.1mm.

[0228] Five replicate test samples were retained and used for subsequent flex bond land area length measurements.

[0229] Flex Bond Landing Area Length Method:

[0230] In order to measure the length of the landing area "S" between two separate adjacent recessed areas (embossings) within a flexural bonding channel, a two-dimensional (2D) line profile (a sub-sampling of a 3D surface image) is extracted as follows. The line profile includes the entire length of the two separate adjacent channel recesses along their central longitudinal axis, and additionally includes a non-recessed area directly adjacent to the leading edge of the first recessed area and the trailing edge of the second adjacent recessed area. Those skilled in the art will appreciate that if the resulting line profile does not generally represent the approximate profile of the flexural bonding channel area due to measurement noise or the presence of localized wrinkling or deformed channels (i.e., channels having a depth of less than 1 mm as determined by the flexural bonding channel depth method described herein), another test position of two adjacent recessed areas of different groups including the flexural bonding channel should be measured so that such artifacts are not present. A height profile of the line is now created (height (mm) vs. line length (mm)). It will be apparent to those skilled in the art that the flexural bonding channel area (minimum Z value) and the non-channel area (maximum Z value adjacent to the channel) are located on the height profile, such as Fig.15 Depicted. This line profile depicts the exemplary length of two adjacent recessed areas within the flexure bonding channel and the length of the distance between them. The distance between adjacent recessed areas is measured as follows from the rear end of the first recessed area to the front end of the second recessed area. Determine the first minimum height value (y-axis) on the line profile within the first recessed area. Now move along the line profile in the z direction to the right of the first minimum height value (y-axis), arrive at a position 100 microns away from the first minimum height value, and set the "first" mark on the line profile. Now determine the second minimum height value (y-axis) on the line profile within the second recessed area. Move along the line profile in the z direction to the left of the second minimum height value (y-axis), arrive at a position 100 microns away from the second minimum height value, and set the "second" mark on the line profile. Now measure the horizontal x distance between the first mark and the second mark placed on the line profile and record it as the length "S" of the flexure bonding landing area, accurate to 0.1mm. Now repeat the entire process until a total of five separate adjacent recessed area pairs of the flexure bonding channel have been analyzed on the test sample. In a similar manner, a total of five separate sets of adjacent recessed area pairs of the flex bond channel are measured on each of the remaining four replicate test samples. The arithmetic mean of all flex bond landing area length values ​​recorded across all five test sample replicates is now calculated and reported as the flex bond landing area length, accurate to 0.1 mm.

[0231] Five replicate test samples were retained and used for subsequent flex bond channel width measurements.

[0232] Flex Bond Channel Width Method:

[0233] To measure the flex bond channel width "A", a two-dimensional (2D) line profile (a sub-sampling of the 3D surface image) is extracted from a position within one of the individual recessed areas within the flex bond channel region perpendicular to the long side of the recess (i.e., the line crosses the width of the recess). The line profile extends across the entire width of the individual channel recess along its central lateral axis and includes non-recessed areas directly adjacent to both sides of the channel. Those skilled in the art will appreciate that if the resulting line profile does not typically represent the approximate profile of the flex bond channel region due to measurement noise or the presence of localized wrinkling or deformed channels (i.e., channels having a depth of less than 1 mm as determined by the flex bond channel depth method described herein), another test position at the individual recessed area of ​​the flex bond channel should be measured so that such artifacts are not present. A height profile of the line is now created (height (mm) vs. line length (mm)). It will be apparent to those skilled in the art that the flex bond channel region (minimum Z value) and the non-channel region (maximum Z value adjacent to the channel) are located on the height profile, such as Fig.15 Depicted. This line profile depicts an exemplary width of the recessed area in the flexure bonding channel. Determine the minimum height value (y-axis) on the line profile. Now move from the minimum height value to a position of 200 microns from the minimum height value in the z direction (y-axis) along the line on the left side of the profile, and set the "left" mark on the line profile. In a similar manner, move from the minimum height value to a position of 200 microns from the minimum height value in the z direction (y-axis) along the line on the right side of the profile, and set the "right" mark on the line profile. Measure the horizontal x distance between the left and right marks placed on the line profile, and record it as the flexure bonding channel width, accurate to 0.1mm. Now repeat the whole process until a total of five separate recessed areas of the flexure bonding channel have been analyzed on the test sample. In a similar manner, measure a total of five separate recessed areas of the flexure bonding channel on each of the remaining four repeated test samples. Now calculate the arithmetic mean of all the flexure bonding channel width values ​​recorded repeatedly across all five test samples, and report it as flexure bonding channel width "A", accurate to 0.1mm.

[0234] Five replicate test samples were retained and used for subsequent flex bond channel depth measurements.

[0235] Flex Bond Channel Depth Method:

[0236] Further prepare the test sample from the flexure bonding channel width method as follows for channel depth measurement.In each of the flexure bonding channel area (left and right), draw a line of about 35mm long on the body-facing surface of the test sample, to describe the position of the flexure bonding channel area depth to be measured, and then the test specimen for bending resistance test will be obtained.The left and right flexure bonding channel area are those regions with the longitudinal direction roughly parallel to the longitudinal axis of the absorbent article.In a similar manner, prepare the remaining four repeated test samples so that a total of ten flexure bonding channel areas (right 5 and left 5) can be analyzed.Digital mark each test sample (that is, iv) so that the test sample can be tracked in each subsequent measurement.

[0237] The thickness of the first test sample is measured at the test position of the non-channelized area defined as the test sample, and the non-channelized area is located between the left flexure bonding channel area and the right flexure bonding channel area and excludes all parts of any flexure bonding channel area present. Ideally, the test position is located at the center of the absorbent article (the intersection of the lateral midpoint and the longitudinal midpoint), and is centered between the left flexure bonding channel area and the right flexure bonding channel area. The thickness of the test sample is mechanically measured using a manually operated micrometer, which is equipped with a pressure foot that can apply a stable pressure of 0.1psi ± 0.01psi (0.69kPa ± 0.07kPa). The manually operated micrometer is a static heavy instrument, and its reading is accurate to 0.01mm. Suitable instruments are Mitutoyo series 543ID-C Digimatic purchased from VWR International, or equivalent. The pressure foot is a flat circular movable surface with a diameter of 25.4mm. The test sample is supported by a horizontal flat reference platform, which is greater than and parallel to the surface of the pressure foot. The micrometer is zeroed for the horizontal flat reference platform. The test sample is placed on the platform, wherein the test position is centered below the pressure foot. Ensure that the presser foot has no part in contact with any part of any flexure bonding channel area present, and then the presser foot is lowered by hand at a rate of descent of 3 ± 1mm / s until all pressure is applied to the sample. After 5 seconds, the thickness is recorded as the absorbent article thickness Ti, accurate to 0.01mm. In a similar manner, the thickness measurement is repeated for all five repeated test samples, and the pad thickness (i.e. Ti-Tv) of each sample is recorded, accurate to 0.01mm. The arithmetic mean of all five repetitions is calculated and reported as the absorbent article thickness T, accurate to 0.01mm.

[0238] The 3D surface topography image of the first test sample i is obtained as follows. The test sample is transferred to the MikroCAD (or equivalent) stage below the camera. The test sample is oriented so that the longitudinal axis of the left and right flexure bonding channel areas is perpendicular to the major axis (X-axis) of the instrument field of view. The 3D surface topography image of the test sample is collected according to the measurement procedure recommended by the instrument manufacturer, which may include focusing the measurement system and performing brightness adjustment. The pre-filtering option is not used. The height image file collected is saved to the evaluation computer running the surface texture analysis software.

[0239] Open the 3D surface topography image in the surface texture analysis software. Then perform the following filtering process on the image: 1) remove invalid points; 2) 3×3 pixel median filtering to remove noise; and 3) 3×3 pixel mean filtering to smooth the surface. Extract two-dimensional (2D) line profiles (subsampling of 3D surface images) from the position perpendicular to the direction of the flexure bonding channel area. The line profile extends across the entire width of the test sample (from left to right) and intersects the left flexure bonding channel area and the right flexure bonding channel area on the test sample at 90 degrees. Draw the line profile so that it intersects with a part of the channel previously drawn during sample preparation of the 35mm line. Those skilled in the art know that if the resulting line profile does not generally represent the approximate outline of the flexure bonding channel area due to measurement noise or the presence of local wrinkling or deformed channels, another test sample should be prepared and measured so that there is no such artifact. Now create the height profile of the line (height (mm) and line length (mm)). It will be apparent to one skilled in the art that the flex bond channel regions (minimum Z values) and non-channel regions (maximum Z values ​​between channels) are located on the height profile, e.g. Fig.15 Depicted. This line profile depicts exemplary depths of flex bond channel regions relative to non-channelized regions located near and between flex bond channel regions present on the test specimen. Export the line height profile raw data to .txt format.

[0240] Enter and process the line height profile raw data in a spreadsheet program such as Excel or equivalent. Determine the Z minimum value of the flexure bond channel area on the left side of test sample i and record it as Zmin iL , accurate to 0.1 mm. In a similar manner, determine the Z minimum value of the flexure bonding channel area on the right side of the test sample i and record it as Zmin iR , accurate to 0.1 mm. The height of the non-channeled area along the line between the left flexure bonding channel area and the right flexure bonding channel area is Zmax i .Zmax iis the calculated arithmetic mean of all height values ​​located along a 10 mm path length centered at the midpoint distance between the left and right flex bond channel regions along the line. However, if the non-channelized region between the left and right flex bond channel regions is too narrow and therefore has a certain level of compression due to the close proximity of the channel regions, a more appropriate non-channelized region would be selected as Zmax i , so that Zmax i The maximum represents the expected height of the non-channelized area of ​​the article within the test sample. i Subtract Zmin from iL The depth of the flexure bond channel area on the left side of the test sample i is calculated and recorded as the left channel depth D iL , accurate to 0.1 mm. In a similar way, by i Subtract Zmin from iR The depth of the flexure bond channel area on the right side of the test sample i is calculated and recorded as the right channel depth D iR , accurate to 0.1 mm. Now calculate D measured for test sample i iL and D iR The arithmetic mean of the values ​​is calculated and recorded as channel depth Di, accurate to 0.1mm. In a similar manner, all five repeated test samples iv are repeated for channel depth measurement, so that a total of ten flexure bonding channel regions (5 right and 5 left) are analyzed, and the channel depth (that is, Di-Dv) of each test sample is recorded, accurate to 0.01mm. Now calculate the arithmetic mean (Di-Dv) of five channel depths calculated for five repeated test samples, and report it as dry channel depth D, accurate to 0.01mm.

[0241] Each numerically labeled replicate test sample was retained for subsequent MD channel bending resistance measurements.

[0242] Flexural Bonding Channel MD Bending Method:

[0243] The MD bending resistance of the prepared test specimens is measured on a universal constant rate extension (CRE) test frame (such as MTS Alliance using TestSuite software, available from MTS Systems Corp., Eden Prairie, MN, or equivalent) or equivalent. The CRE test frame is equipped with a 3-point bending fixture and a load cell for which the measured force is within 1% to 99% of the load cell (preferably a 10N load cell) limit. The bottom fixed fixture consists of two cylindrical rods of 3.175 mm in diameter and 110 mm in length made of polished stainless steel, with frictionless roller bearings mounted at both ends of each rod. The two rods are mounted horizontally, aligned front to back and parallel to each other, with the top radius of the rods aligned vertically and freely rotating around the diameter of the cylinder through frictionless bearings. In addition, the fixture allows the two rods to move horizontally away from each other on the track so that a gap can be set between them while maintaining their orientation. The top fixture consists of a third cylindrical rod also of 3.175 mm diameter and 110 mm long, made of polished stainless steel, with frictionless roller bearings mounted on both ends. When in proper position, the rod of the top fixture is parallel to and aligned front-to-back with the rod of the bottom fixture, and centered between the rods of the bottom fixture. Both fixtures include an integral adapter adapted to be mounted in corresponding locations on a universal test frame and locked into position so that the rod is orthogonal to the motion of the test frame crossbar.

[0244] Test specimens for bending resistance measurement were prepared as follows from digitally marked test specimens previously prepared for flexural bonding channel depth measurement. Each individually prepared test specimen was 5.3 mm wide and had a length of at least 35 mm. The width of the test specimen was centered on the width of the flexural bonding channel area, and the length of the test specimen was parallel to the longitudinal direction of the channel. The test specimen included a channel area, wherein a 35 mm line was pre-drawn in the channel during sample preparation. Two test specimens were prepared from each digitally marked test specimen; one from the flexural bonding channel area on the left side of the test specimen, and one from the flexural bonding channel area on the right side of the test specimen. Each test sample was obtained from the same area of ​​the flexural bonding channel area where the channel depth was previously analyzed, represented by the 35 mm line drawn during sample preparation. A total of ten flexural bonding channel area test specimens (5 on the left and 5 on the right) were prepared and digitally marked (i.e., i L -v L and i R -v R ).

[0245] Set the gap between the bars of the lower fixture ("span") to 20 mm ± 0.5 mm (center of bar to center of bar), with the upper bar centered at the midpoint between the lower bars. Load the first test specimen i L , with its long sides perpendicular to the two lower bars of the clamp and resting on them, ensuring that it is centered under the upper bar with the body-facing surface of the test specimen facing the upper bar. Move the vertical position of the upper bar until the bottom edge of the upper bar is 1 mm above the test specimen surface, then return the clamp position to zero.

[0246] The universal test frame for flexural bending testing was programmed to move the clamps so that the top fixture moves downward relative to the lower fixture at a rate of 1.0 mm / sec, a total distance of 12 mm from the zero position. The clamps were then immediately returned to the original gauge length at a rate of 1.0 mm / sec. Force (N) and displacement (mm) data were collected continuously at 50 Hz throughout the test. The test specimen width was recorded as 5.3 mm. The test was started and time, force, and displacement data were collected continuously.

[0247] For test specimen i L , plot a graph of force (N) versus displacement (mm). From this graph, determine the maximum peak force and record it as Flex Bond Channel MD Peak Load MD Peak iL , accurate to 0.01 N. The slope of the initial linear portion of the curve before the peak is calculated and recorded as the flexural bond channel MD bending resistance iL , accurate to 0.005N / mm. The peak energy is calculated as the area under the force-displacement curve from the initial point to the peak force and recorded as the flexural bond channel MD energy to the peak MD PE iL , accurate to 0.01N*mm. In a similar manner, test specimen i taken from the right channel of test sample i R Repeat the whole process. Now calculate for the left side i L and right side i R The values ​​obtained for each parameter of the test specimens are the arithmetic mean and recorded as the Dry MD Peak i , accurate to 0.01N; dry MD bending resistance i , accurate to 0.005N / mm; and dry MD PE i , accurate to 0.01 N*mm. In a similar manner, all ten flexure bond channel area test specimens taken from test sample iv (i L -v L and i R -v R) Repeat the process. Calculate the arithmetic mean of each parameter of the values ​​obtained for test sample iv and report as Dry MD Peak, accurate to 0.01 N; Dry MD Flexural Resistance, accurate to 0.005 N / mm; and Dry MD Peak Energy PE, accurate to 0.01 N*mm.

[0248] Flexure Bonded Channel CD Anti-bending Method:

[0249] The CD bend resistance of a set of freshly prepared test specimens was measured on the same common rate of extension (CRE) test frame using the same 3-point bend fixture and load cell as previously described for the MD bend resistance measurements.

[0250] Prepare a new set of test specimens as follows. If necessary, unfold the absorbent article, then remove the protective cover on the panty adhesive (i.e. wrapping paper or release paper). A thin layer of talcum powder is applied to the adhesive to alleviate tackiness. The test specimen has a width of 25.4mm (parallel to the longitudinal axis of the article) and a length equal to the distance (about 70mm) from the left edge of the article to the right edge. The test specimen is taken from the area of ​​the article, wherein the flexure bonding channel area is parallel to the longitudinal axis orientation of the article, and the selected area does not contain the residue of folds or wrinkles. Ideally, the test specimen is obtained from the center of the article (the intersection of the longitudinal midline and the transverse midline). Ten repeated test specimens have been prepared in total. The test specimen is mounted on a 3-point bending fixture so that five "channelization" repeats will be bent along the bonding channel (i.e., the upper center blade will be parallel to the channel and centered on the channel), and the other five "non-channelization" repeats will be bent along the non-channelization area of ​​the test specimen.

[0251] The gap ("span") between the bars of the lower fixture is set to 25mm ± 0.5mm (center of bar to center of bar), with the upper bar centered at the midpoint between the lower bars. The first "channelized" test specimen is installed so that it rests on the two lower bars of the fixture, with the lateral outer edges of the test specimen parallel to the bar orientation. The position of the test specimen is adjusted so that the bonding channel is parallel to the upper bar and centered below the upper bar, with the body-facing surface of the test specimen facing the upper bar. In this position, the test sample will bend along the flexural bonding channel area. Move the vertical position of the upper bar until the bottom edge of the upper bar is 1mm above the test specimen surface, and then return the clamp position to zero. The universal test frame for flexural bending tests is programmed to move the clamp so that the top clamp moves downward at a rate of 1.0mm / sec relative to the lower clamp, with a total distance of 12mm from the zero position. The clamp is then immediately returned to the original gauge length at a rate of 1.0mm / s. Force (N) and displacement (mm) data are continuously collected at 50Hz throughout the test. The test specimen width was recorded as 25.4 mm. The test was started and time, force and displacement data were continuously collected.

[0252] For the "channelized" test specimen, plot a graph of force (N) versus displacement (mm). Calculate the slope of the initial linear portion of the curve and record it as the Dry Flex Bond Channel CD Bend Resistance, accurate to 0.005 N / mm. In a similar manner, repeat the entire process for a total of five "channelized" test specimens. Now calculate the arithmetic mean of the slope values ​​for the five "channelized" test specimens and report it as the Dry Flex Bond Channel CD Bend Resistance, accurate to 0.005 N / mm.

[0253] The "non-channelized" test specimen is tested in a similar manner, except that the test specimen is positioned. The "non-channelized" specimen is mounted on a 3-point bending fixture so that it rests on the two lower rods of the fixture, wherein the lateral outer edges of the test specimen are parallel to the rod orientation. The position of the test specimen is adjusted so that the non-channelized area of ​​the test specimen is centered below the upper rod, wherein the body-facing surface of the test specimen faces the upper rod. In this position, the test specimen will bend along an area that does not contain any part of the flexure bonding channel area. Move the vertical position of the upper rod until the bottom edge of the upper rod is 1mm above the test specimen surface, and then the clamp position is zeroed. Then perform the test as described above, and continuously collect time, force and displacement data.

[0254] For the "Non-Channeled" test specimen, plot a graph of Force (N) versus Displacement (mm). Calculate the slope of the initial linear portion of the curve and record it as the Dry Non-Channeled CD Flexural Resistance to the nearest 0.005 N / mm. Repeat the entire process in a similar manner for a total of five "Non-Channeled" test specimens. Now calculate the arithmetic mean of the slope values ​​for the five "Non-Channeled" test specimens and report it as the Dry Non-Channeled CD Flexural Resistance to the nearest 0.005 N / mm.

[0255] Examples / Data

[0256] Provide following data and embodiment (comprising comparative example) to help illustrate upper nonwoven layer and lower nonwoven layer, absorbent core structure and / or absorbent article described herein.Illustrated structure is provided only for illustrative purposes and can not be understood as limitation to the present disclosure, because can have many variations when not departing from the spirit and scope of the present invention.

[0257] Nonwoven Material Testing

[0258] The nonwoven layer material is tested to evaluate the ability of the nonwoven material to strain (elongate) and recover its initial state (simulating physical deformation in use) under balanced stretching. Samples FH are comparative examples. The CD cyclic extension to 3% strain method and the breaking strain method described herein are tested. The results are shown in Table 1.

[0259] Table 1: Nonwoven materials tested in the CD cyclic extension to 3% strain method and the break strain method

[0260]

[0261] 1 ATB Z87G-40 was purchased from Xiamen Yanjan New Material Co. (China)

[0262] 2 by 53FC041001 purchased from Sandler GmbH (Germany)

[0263] 3 by 553FC041005 (option 82) from Sandler GmbH (Germany)

[0264] 4 Purchased from Xiamen Yanjan New Material Co. (China) as Aura 20

[0265] 5 Purchased from Jacob Holms Industries (Germany) as S25000541R01

[0266] 6 PFNZN 18G BICO8020 PHI 6 was purchased from dPFNonwovens Czech SRO (Czech Republic)

[0267] 7 PEGZN25 BICO7030 Phobic was purchased from dPFNonwovens Czech SRO (Czech Republic)

[0268] 8 Purchased from Dunn Paper (USA) at 3028

[0269] It is found that suitable nonwoven layer materials are strained (stretched) with balanced stretching to recovery behavior. If the nonwoven layer material plastically stretches (that is, stretches but does not recover) as the fluff / AGM matrix in the inner core layer stretches, then there will not be enough recovery energy to return to the initial, pre-stretched state, and the nonwoven layer material will become permanently strained (stretched). The top nonwoven layer of the present disclosure can have a permanent strain value less than about 0.013. At the same time, if the nonwoven layer material is strained violently, for example, greater than 5%, the nonwoven layer material needs to maintain its integrity and not tear or break (see, for example, sample H, which tears and has a break strain less than 5%). The nonwoven layer of the present disclosure can have a break strain greater than about 10%.

[0270] The above nonwoven layer materials were also tested to evaluate the ability of the nonwoven material to bend and deform and to recover to its original state. The test was performed according to the wet and dry CD ultrasensitive 3-point bending method described herein. The results are shown in Table 2.

[0271] Table 2: Nonwoven materials tested in wet and dry CD ultrasensitive 3-point bending method

[0272] sample Dry Peak Load Dry bending energy Dry recovery energy N N*mm N*mm A 0.07 0.219 0.092 B 0.38 1.015 0.291 C 0.26 0.595 0.201 D 0.09 0.176 0.036 E 0.03 0.059 0.032 F 0.01 0.0216 0.005 G 0.03 0.0624 0.019 H 0.04 0.0734 0.031

[0273] During walking, the absorbent article is compressed and bent left and right in a cyclic mode when the gap between her legs narrows, and then expands as her legs move. Not limited by theory, it is believed that the nonwoven layer material with dry bending energy less than about 2N*mm will allow this bending compression to occur easily, but will not be too hard to hinder bending compression. At the same time, after bending compression, the nonwoven layer needs to be able to maintain enough dry recovery energy so that the fluff / AGM matrix in the nonwoven layer and the inner core layer returns to its initial pre-bent state. The upper nonwoven layer of the present disclosure can have a dry recovery energy value greater than about 0.03N*mm.

[0274] Sample AE shows the dry peak load of 0.03N to 0.38N and the dry recovery energy of 0.032N*mm to 0.092N*mm, indicating that these materials are easy to bend and have enough dry recovery energy to recover their initial pre-bent state. As comparative examples, sample F and G show the dry peak load of 0.01N and 0.03N respectively and the dry recovery energy of 0.005N*mm and 0.019N*mm respectively, which shows that although these materials are easy to bend, they do not have enough recovery energy to recover their initial pre-bent state after compression. Sample H (comparative example) shows the dry peak load of 0.04N and the dry recovery energy of 0.031N*mm. However, it is found that sample H tears when getting wet, so that it is not enough to be used as the upper nonwoven layer and / or the lower nonwoven layer of the present disclosure.

[0275] Without being limited by theory, it is believed that the nonwoven layer material comprising thick fibers (about 2.0 dtex to about 10 dtex) arranged in a network structure is able to carry mechanical loads within the fiber network and return the absorbent core structure and / or absorbent article to its original shape after bending compression. Samples F and G comprise relatively fine fibers (less than about 2.0 dtex), while samples AE comprise a fiber blend having a fiber thickness of about 2.2 dtex to about 10 dtex.

[0276] Absorbent core structure test

[0277] The absorbent core structure is tested to evaluate the ability of the absorbent core structure to compress (simulate the compression experienced between the legs of the wearer) and return to its original state. The examples 1-3 in Table 3 show the absorbent core structures described herein. Comparative Examples AC are comparative examples. The descriptions of Examples 1-3 and Comparative Examples AC are listed in Table 3. The absorbent core structure is prepared as described below. The absorbent core structure is evaluated according to the wet and dry gathered compression method as described herein. The results are shown in Table 4.

[0278] Table 3: Absorbent core structure

[0279]

[0280] 1 ATB Z87G-40 was purchased from Xiamen Yanjan New Material Co. (China)

[0281] 3 by 553FC041005 (option 82) from Sandler GmbH (Germany)

[0282] 4 Purchased from Xiamen Yanjan New Material Co. (China) as Aura 20

[0283] 5 Purchased from Jacob Holms Industries (Germany) as S25000541R01

[0284] 6 PFNZN 18G BICO8020 PHI 6 was purchased from dPFNonwovens Czech SRO (Czech Republic)

[0285] 8 Purchased from Dunn Paper (USA) at 3028

[0286] 9 Purchased from Evonik (Germany) as Favor SXM9745

[0287] 10 Purchased from Resolute Alabama (USA) as Item 9E3-COOSABSORB S

[0288] 11 Purchased from Fitesa (Germany) as Article 4004416 (MR 3585374)

[0289] The absorbent core structure listed in Table 3 is produced as described in detail in the specification. Specifically, first the upper nonwoven layer is introduced on the forming drum in the shelf section, and is pulled into a three-dimensional pocket shape under vacuum. The uniform flow of fluff (cellulose) and AGM material is directly deposited on the upper nonwoven layer in the forming station. Before entering the forming station, the upper nonwoven is coated with a spray adhesive (available from the Technomelt DM 9036U of Henkel (Germany), 6gsm continuous melt-blown spiral, 50mm is wide), to provide fluff (cellulose) and AGM and the stronger connection of the upper nonwoven, and do not hinder liquid from flowing into the fluff / AGM matrix. When leaving the shelf section, the lower nonwoven web is combined with the nonwoven of the uniform blend carrying fluff / AGM. The lower nonwoven was pre-coated with adhesive (Technomelt DM 9036U from Henkel (Germany)) to achieve a perimeter seal (10 gsm meltblown spiral, 20 mm wide on the sides), and a 6 gsm, 50 mm wide continuous meltblown spiral adhesive (Technomelt DM 9036U from Henkel (Germany)) was applied in the center to better integrate the fluff / AGM matrix.

[0290] Examples 1 to 3 and Comparative Examples A and B also have Figure 4 The structural bonding shown is Figure 5 The profile shown. Examples 1-3 and Comparative Examples AB have a structural bond spacing of 32 mm x 16 mm, resulting in a total structural bond site area of ​​1.38% of the total absorbent core structural area. Comparative Example C is the same as Comparative Example B, except that the structural bond spacing is 10 mm x 10 mm, resulting in a total structural bond site area of ​​6.28% of the total absorbent core structural area. The structural bonds are applied using a heated aluminum mold to produce the embossing pattern in a heated hydraulic press. The structural bond embossing plate has an area of ​​3.55 mm 2 And the height is about 1mm protrusion, such as Figure 4 As shown, Figure 5 The structural bonds were spaced according to the spacing dimensions described above. The structural bonding embossing plate was heated to 120°C and set to a compression pressure of 170 kPa. The absorbent article was placed and oriented under the heated embossing plate on the bottom plate of the hydraulic press and a thin sheet of Teflon was placed before embossing. TM The film was placed on the sample to avoid melting of the top sheet fibers. The hydraulic press was started and compressed the sample for a dwell time of 1.7 seconds to create a structural bond pattern.

[0291] Examples 1-3 and Comparative Examples AC also have Fig. 7AThe flex bond channel areas are applied with a heated aluminum die to produce the embossed pattern in a heated hydraulic press. The flex bond channel embossing plate has protrusions spaced about 1.5 mm apart and are about 3 mm long and about 1.5 mm wide. The bond channel embossing plate is heated to 120°C and set to a compression pressure of 200 kPa. The absorbent article is placed and oriented under the heated embossing plate on the bottom plate of the hydraulic press and a thin piece of Teflon is placed before embossing. TM The film was placed on the sample to avoid melting of the top sheet fibers. The hydraulic press was started and compressed the sample for a dwell time of 1.7 seconds to produce a knot embossing pattern.

[0292] Table 4: Absorbent core structures measured in wet and dry gathered compression methods

[0293]

[0294] The absorbent core structure that discovery comprises the nonwoven layer material with enough elasticity and recovery energy can return to the original absorbent core structure shape before compression.Embodiment 1-3 shows the fifth cycle wet recovery energy greater than 1.0N*mm and the fifth cycle wet maximum compression force of 207gf to 213gf.These structures show low compression force (less resistance, so it feels soft and pliable), but still can recover their shape when the structure is compressed and released in a cyclic manner.However, Comparative Example A-C shows the fifth cycle wet recovery energy of 0.26N*mm to 0.59N*mm.There is not enough recovery energy after five compression cycles, and Comparative Example A-C keeps compression, gathers state with the power (stored energy) that is not enough to recover its original shape before compression.

[0295] The absorbent core structures and / or absorbent articles of the present disclosure may have a fifth cycle wet recovery energy greater than about 1.0 N*mm, or from about 1.0 N*mm to about 3.5 N*mm. The absorbent core structures and / or absorbent articles of the present disclosure may have a fifth cycle wet maximum compression force greater than about 150 gf, preferably greater than about 200 gf, or from about 150 gf to about 225 gf.

[0296] It was found that although the nonwoven material alone may have sufficient % strain at break in the strain at break method, once combined into an absorbent core structure, the nonwoven material may not be able to provide sufficient recovery energy for the complete absorbent core structure (such as, for example, in Comparative Example A) to return to its original pre-compression shape. For example, in Comparative Example A, the basis weight and thickness of the fibers of the upper nonwoven material provide a fifth cycle wet recovery energy of less than 1.0 N*mm when combined with a thin lower nonwoven material.

[0297] Finished product testing

[0298] Absorbent articles are tested to evaluate the ability of the wrapped absorbent core structure to compress (simulate the compression experienced between the legs of the wearer) and return to its original state. Examples 4-7 show absorbent articles as described herein. Comparative Examples D and E are comparative examples. Comparative Example FL is a commercially available finished product. The descriptions of Examples 4-7 and Comparative Examples DE are listed in Table 5a. The description of Comparative Example FL is listed in Tables 5b and 5c. Examples 4-7 and Comparative Examples D and E are prepared as described below. The absorbent articles in Tables 5a and 5b are evaluated according to the wet and dry CD and MD 3-point bending method, the wet and dry gathered compression method, and the light touch rewetting method as described herein. The results are shown in Table 6.

[0299] Table 5a: Absorbent article description

[0300]

[0301] 1 ATB Z87G-40 was purchased from Xiamen Yanjan New Material Co. (China)

[0302] 2 by 53FC041001 purchased from Sandler GmbH (Germany)

[0303] 3 by 553FC041005 (option 82) from Sandler GmbH (Germany)

[0304] 4 Purchased from Xiamen Yanjan New Material Co. (China) as Aura 20

[0305] 5 Purchased from Jacob Holms Industries (Germany) as S25000541R01

[0306] 6 PFNZN 18G BICO8020 PHI 6 was purchased from dPFNonwovens Czech SRO (Czech Republic)

[0307] 8 Purchased from Dunn Paper (USA) at 3028

[0308] 9 Purchased from Evonik (Germany) as Favor SXM9745

[0309] 10Purchased from Resolute Alabama (USA) as Item 9E3-COOSABSORB S

[0310] 12 The nonwoven top sheet "Nonwoven SG" is a nonwoven web according to U.S. Patent Publication No. 2019 / 0380887.

[0311] Table 5b: Commercially available finished products:

[0312] Example Commercially available products size When producing Comparative Example F Always Ultra Size 2 Canada Comparative Example G Stayfree Ultra Length USA Comparative Example H U×K (Kotex Security) Length USA Comparative Example 1 Body shape Length U.K. Comparative Example J Kao Laurier F Length Japan Comparative Example K Unicharm Sofy Naked Feel Size rules Japan Comparative Example L Always Infinity Size 2 Canada

[0313] Table 5c: Materials found in commercially available products (Comparative Examples F to L)

[0314]

[0315] Examples 4 to 7 and Comparative Examples D and E include structures as detailed in Table 3 as in Examples 1 to 3, with the same adhesive design and the same 32 mm × 16 mm structural bonding pattern in the absorbent core structure (the total structural bonding area is 1.38% of the total area of ​​the absorbent core structure). In addition, the absorbent article includes a nonwoven top sheet web as detailed in U.S. Patent Publication No. 2019 / 0380887, which is bonded to the absorbent core structure with a spray adhesive application (Technomelt DM 9036U purchased from Henkel (Germany), 3gsm continuous meltblown spiral, 50mm wide, 150mm long). In addition, a 12gsm polypropylene backsheet is bonded to the outward-facing surface of the lower nonwoven with a spray adhesive application (Technomelt DM 9036U purchased from Henkel (Germany), 3gsm continuous meltblown spiral, 50mm wide, 150mm long).

[0316] Examples 4-7 and Comparative Examples D and E also have Figure 4 The structural bonding shown is Figure 5 The profile shown. Structural bonding is applied using a heated aluminum die to create the embossing pattern within a heated hydraulic press. The structural bonding embossing press plate has an area of ​​3.55mm 2 And the height is about 1mm protrusion, such as Figure 4 As shown, Figure 5 The structural bonds were spaced according to the spacing dimensions described above. The structural bonding embossing plate was heated to 120°C and set to a compression pressure of 170 kPa. The absorbent article was placed and oriented under the heated embossing plate on the bottom plate of the hydraulic press and a thin sheet of Teflon was placed before embossing. TM The film was placed on the sample to avoid melting of the top sheet fibers. The hydraulic press was started and compressed the sample for a dwell time of 1.7 seconds to create a structural bond pattern.

[0317] Prior to backsheet bonding, flex bond channel regions were applied to Examples 4-7 and Comparative Examples D and E, which had Fig. 7A The flex bond channel area was applied with a heated aluminum die to produce the embossed pattern in a heated hydraulic press. The flex bond channel embosser plate had protrusions spaced about 1.5 mm apart and were about 3 mm long and about 1.5 mm wide. The bond channel embosser plate was heated to 120°C and set to a compression pressure of 200 kPa. The absorbent article was placed and oriented under the heated embosser plate on the bottom plate of the hydraulic press and a thin piece of Teflon was placed on top prior to embossing. TM The film was placed on the sample to avoid melting of the top sheet fibers. The hydraulic press was started and compressed the sample for a dwell time of 1.7 seconds to produce a knot embossing pattern.

[0318] Table 6: Tested in wet and dry CD and MD 3-point bend method, wet and dry gathered compression method and light touch rewet method Absorbent products and commercially available finished products

[0319]

[0320]

[0321] It is believed that in order to provide high body conformability, the absorbent articles of the present disclosure may exhibit a strength of about 10 N.mm 2 To about 30N.mm 2 , or about 10N.mm 2 To about 25N.mm 2 In addition, it is believed that in order to provide an absorbent article that can be compressed with body movement and recover to its original pre-compression state against the user's body, the absorbent article of the present disclosure can have a fifth cycle wet recovery energy of about 1.0 N.mm to about 3.5 N.mm and / or a fifth cycle wet recovery of about 29% to about 40%. The absorbent article of the present disclosure can also maintain good fluid handling, which delivers a low light touch rewet of about 0g to about 0.15g.

[0322] Examples 4-7 showed 13.0 N.mm in both wet and dry bunched compression methods. 2 Up to 18.7N.mm 2 CD dry bending stiffness and 5th cycle wet recovery of 29% to 36%, demonstrating that these structures will be able to maintain their shape in use. Comparative Examples D and E exhibited 9.1 N.mm 2 and 13.0N.mm 2 CD dry bending stiffness. However, Comparative Examples D and E exhibited a fifth cycle wet recovery of less than 29% in the wet and dry bunched compression method, indicating that these structures will not be able to maintain their shape in use and will remain bunched. Comparative Example FL exhibited 29 N.mm 2Up to 47.5N.mm 2 The CD dry bending stiffness of is (indicating that the structure is less flexible and less able to conform), which is a commercially available product.

[0323] Without being limited by theory, it is believed that in order to maintain comfortable shape recovery after compression, sufficient recovery energy is required to push the absorbent article on the underwear back to its pre-compression shape. At the same time, the absorbent article (via the absorbent core structure) needs to recover along the same path as the compression to return to its pre-compression position. If the fifth cycle wet recovery energy is less than about 1.0N.mm, the absorbent article may not have the recovery energy required to recover its shape. If the fifth cycle wet recovery energy value is too high, the recovery may be too strong, making the wearer feel like the absorbent article is not staying in place. If the fifth cycle wet recovery % value is low (less than about 29%), the absorbent article may not return to its pre-compression shape and may remain deformed and gathered. If the fifth cycle wet recovery % value is too high (greater than about 40%), it indicates that when the absorbent article is first applied to the wearer's underwear, the absorbent article may be too strongly restored to a flat shape, which is contrary to the shape that fits her body.

[0324] Structural Bond Testing

[0325] The absorbent core structures were tested to evaluate the effect of structural bonding area on flexibility and bending stiffness. Example 8 did not feature any structural bonding within the absorbent core structure. Examples 9 and 10 had Figure 4 The structural bonding shown is Figure 5 The results of the wet and dry MD 3-point bend method are shown in Table 7.

[0326] Table 7: Polypropylene films according to the present invention with different structural bonding areas tested in wet and dry CD and MD 3-point bend method Absorbent core structure.

[0327]

[0328] 3 by 553FC041005 (option 82) from Sandler GmbH (Germany)

[0329] 9 Purchased from Evonik (Germany) as Favor SXM9745

[0330] 10 Purchased from Resolute Alabama (USA) as Item 9E3-COOSABSORB S

[0331] 13 Purchased from Industries SpA. (Italy) at 10SMS PHILIC

[0332] Table 7 demonstrates the effect of total structural bond area and spacing. Figure 4 The asymmetric structure bonding shape shown and Figure 5 The profile shown has a 3.55mm 2 The maximum area of ​​the MD dry bending stiffness was found to increase with the increase of the structural bonding area. Example 8 showed 9.8 N.mm 2 MD dry bending stiffness with non-structural bonding. Example 9 exhibits 19.2 N.mm 2 MD dry bending stiffness of 32mm x 16mm with a structural bond spacing (total structural bond site area is 1.38% of the total absorbent core structure area). Example 10 exhibits 29.6N.mm 2 MD dry bending stiffness with a structural bond spacing of 16 mm x 16 mm (the total structural bond site area is 3.96% of the total area of ​​the absorbent core structure). It is believed that in order to maintain a flexible and conformable absorbent core structure and / or absorbent article in the front-to-back (MD) direction of wear, the absorbent core structure and / or absorbent article may have a MD dry bending stiffness of about 10 N.mm 2 To about 30N.mm 2 MD stem bending stiffness.

[0333] The absorbent core structure listed in Table 7 is produced as described in detail in the specification. Specifically, first 50gsm elastic jet spunlace 6 upper nonwoven fabric is introduced on the forming drum in the shelf section, and is pulled into a three-dimensional pocket shape under vacuum. The uniform flow of fluff (cellulose) and AGM material is directly deposited on the upper nonwoven material in the forming station. Before entering the forming station, the upper nonwoven fabric is coated with a spray adhesive (available from the Technomelt DM 9036U of Henkel (Germany), 6gsm continuous melt-blown spiral, 50mm is wide), to provide fluff (cellulose) and AGM and the stronger connection of the upper nonwoven fabric, and do not hinder liquid from flowing into the fluff / AGM agglomerate. When leaving the shelf section, the nonwoven fabric combination of the 10gsm SMS bottom nonwoven web and the uniform blend carrying fluff (cellulose) and AGM layer. The lower nonwoven was pre-coated with adhesive (Technomelt DM 9036U from Henkel (Germany)) to achieve a perimeter seal (10 gsm meltblown spiral, 20 mm wide on the sides) and a 6 gsm, 50 mm wide continuous meltblown spiral adhesive (Technomelt DM 9036U from Henkel (Germany)) was applied in the center to better integrate the fluff / AGM mass. Figure 4 The structural bonding shown is Figure 5The profile shown is applied to Examples 9 and 10. The structural bonding of Example 9 has a spacing of 32mm×16mm, thereby occupying a total structural bonding position area of ​​1.38% of the total area of ​​the absorbent core structure. The structural bonding of Example 10 has a spacing of 16mm×16mm, thereby occupying a total structural bonding position area of ​​3.96% of the total area of ​​the absorbent core structure with this structural bonding profile. The total area of ​​the absorbent core structure is measured according to the structural bonding position pattern spacing and area measurement method. Structural bonding is applied using the same method as described above for Examples 1-3 and Comparative Examples AB.

[0334] Flex Bond Channel Area Testing

[0335] Absorbent articles are tested to assess the influence of the flexure bonding channel area on MD and CD dry bending resistance. Specifically, absorbent articles are tested to assess the ability of the flexure bonding channel area to bend in MD (i.e. longitudinal (or front and back) direction) (see Table 9) and the ability to bend in the CD (left and right) direction (see Table 10). Example 11 shows absorbent articles as described herein. Comparative Example MQ is a commercially available finished product with embossed channels. The description of Example 11 is listed in Table 8a. The description of Comparative Example MQ is listed in Tables 8b and 8c. Example 11 is prepared as described in Table 5a above for Example 4. Example 11 and Comparative Example MQ are evaluated according to the flexure bonding channel depth method and the flexure bonding channel MD bending resistance method, and the results are shown in Table 9. Example 11 is also evaluated according to the flexure bonding channel CD bending resistance method, and the results are shown in Table 10.

[0336] Table 8a: Absorbent article description

[0337]

[0338] 1 ATB Z87G-40 was purchased from Xiamen Yanjan New Material Co. (China)

[0339] 6 PFNZN 18G BICO8020 PHI 6 was purchased from dPFNonwovens Czech SRO (Czech Republic)

[0340] 9 Purchased from Evonik (Germany) as Favor SXM9745

[0341] 10 Purchased from Resolute Alabama (USA) as Item 9E3-COOSABSORB S

[0342] 12 The nonwoven top sheet "Nonwoven SG" is a nonwoven web according to U.S. Patent Publication No. 2019 / 0380887.

[0343] Table 8b: Commercially available finished products

[0344]

[0345] Table 8c: Materials found in commercially available products (Comparative Examples M to Q)

[0346]

[0347] Table 9: Absorbent articles tested in the Flex Bond Channel Depth Method and the Flex Bond Channel MD Resistance Method Commercially available finished products

[0348]

[0349] It is found that embodiment 11 has a well-defined flexure bonding channel area, which shows a depth to thickness ratio of 69%, but only requires a small bending force of 0.0969N, and the dry MD bending resistance is only 0.0244N / mm. In contrast, comparative example MQ has a depth to thickness ratio between 33% and 66%, and requires a bending force of 0.2074N to 0.518N. Comparative example MQ also shows a dry MD bending resistance of 0.0459 to 0.1305, indicating that the channel-shaped structure in these products has higher bending resistance (that is, less flexible). Not limited by theory, it is believed that the consumer wearing the absorbent article depicted in embodiment 11 will experience the product that conforms to her body with less resistance and pressure on her body, and therefore will experience a tighter and more comfortable conformable absorbent article.

[0350] Table 10: Absorbent articles tested in the Flex Bond Channel CD Bend Method

[0351]

[0352] It is found that the dry flexure bonding CD bending resistance in the flexure bonding channel area is lower than the dry flexure bonding CD bending resistance in the non-channelized area adjacent to the flexure bonding channel area. Example 11 shows a CD bending resistance index of 1.7 (ratio of dry non-channelized CD bending resistance to dry flexure bonding CD bending resistance). This confirms that the flexure bonding channel area can be easily bent at the channel with lower CD bending resistance. Viewing Tables 9 and 10 together, it is found that the dry CD bending resistance and dry MD bending resistance values ​​of Example 11 are comparable and significantly lower than Comparative Example MQ. Example 11 shows low bending resistance in both MD and CD directions, so it is believed that Example 11 will be able to conform to a wide range of anatomical body shapes tightly and comfortably.

[0353] Combination / Example

[0354] Paragraph A. A disposable absorbent article, comprising: a front end region, a rear end region, and an intermediate region disposed between the front end region and the rear end region; a top sheet; a back sheet; an absorbent core structure disposed between the top sheet and the back sheet, wherein the absorbent core structure comprises: (a) an upper nonwoven layer, the upper nonwoven layer comprising polymer fibers; (b) a lower nonwoven layer, the lower nonwoven layer comprising polymer fibers; and (c) an inner core layer disposed between the upper nonwoven layer and the lower nonwoven layer, wherein the inner core layer comprises fibers. cellulose fibers and superabsorbent particles; and a flexural bond channel region formed in at least the middle region, wherein the flexural bond channel region has a dry channel depth of at least 1.0 mm and a channel width of about 1.0 mm to about 3.0 mm; and wherein the flexural bond channel region has a CD flexural index of about 1.1 to about 3.0, and a dry MD flexural resistance of less than about 0.04 N / mm, preferably about 0.005 N / mm to about 0.035 N / mm, as measured according to the Flexural Bond Channel MD Flexural Resistance Method.

[0355] Paragraph B. The disposable absorbent article of Paragraph A, wherein the flex bond channel region has a minimum channel length of at least about 50 mm.

[0356] Paragraph C: A disposable absorbent article according to paragraph A or B, wherein the flex bond channel area includes one or more flex bond embossments and one or more flex bond landing areas arranged between each of the flex bond embossments.

[0357] Paragraph D. A disposable absorbent article according to Paragraph C, wherein the thickness "T2" of each of the flex bond land areas may be between about 50% and about 70% of the thickness "T" of the absorbent article.

[0358] Paragraph E. A disposable absorbent article according to Paragraphs C to D, wherein the flex bond embossment has an embossment area and the flex bond channel region has a channel area, wherein the embossment area is 22% to 65% of the channel area.

[0359] Paragraph F. The disposable absorbent article of any of Paragraphs C to E, wherein the flex bond embossments have an embossment length of about 1.0 mm to about 4.0 mm.

[0360] Paragraph G. The disposable absorbent article of any of Paragraphs C to F, wherein each of the flex bond land areas has a length of about 0.5 mm to about 4 mm.

[0361] Paragraph H. The disposable absorbent article of any of Paragraphs A to G, wherein the absorbent article comprises an inner flex bond channel region and an outer flex bond channel region.

[0362] Paragraph I. The disposable absorbent article of any of Paragraphs A to H, wherein the absorbent article has an average density between about 0.045 g / cm3 and about 0.15 g / cm3.

[0363] Paragraph J. The disposable absorbent article of any of Paragraphs A to I, wherein the upper nonwoven has a basis weight of about 35 gsm to about 85 gsm.

[0364] Paragraph K. The disposable absorbent article of any of Paragraphs A to J, wherein the lower nonwoven has a basis weight of about 10 gsm to about 40 gsm.

[0365] Paragraph L. The disposable absorbent article of any of Paragraphs A to K, wherein the inner core layer comprises from about 125 to about 400 gsm of cellulosic fibers.

[0366] Paragraph M. A disposable absorbent article according to any of paragraphs A to L, wherein the inner core layer comprises from about 50% to about 85% cellulose fibers, by weight of the inner core layer, and from about 15% to about 50% superabsorbent particles, by weight of the inner core layer.

[0367] Paragraph N. A disposable absorbent article according to any of paragraphs A to M, wherein the absorbent article has a CD Dry Bending Stiffness between about 10 N.mm2 and about 30 N.mm2 as measured by the Wet and Dry CD and MD 3-Point Bend Method, and a Fifth Cycle Wet Recovery % between about 29% and about 40% as measured by the Wet and Dry Gather Compression Method.

[0368] Paragraph O. A disposable absorbent article according to any one of Paragraphs A to N, wherein the flex bond channel region has a 0.05 g / cm 3 Up to 0.3g / cm 3 channel density.

[0369] Paragraph P. A disposable absorbent article according to any one of paragraphs A to O, wherein the absorbent article further comprises a structural bonding site; wherein the structural bonding site has a thickness of about 2 mm. 2 To about 5mm 2 bonding area.

[0370] Q. A disposable absorbent article comprising: a topsheet; a backsheet; an absorbent core structure disposed between the topsheet and the backsheet; wherein the topsheet forms the wearer-facing surface of the absorbent article and the backsheet forms the outward-facing surface of the absorbent article; wherein the absorbent core structure comprises: (a) an upper nonwoven layer comprising polymer fibers; (b) a lower nonwoven layer comprising polymer fibers; and (c) an inner core layer disposed between the upper nonwoven layer and the lower nonwoven layer; wherein the inner core layer comprises cellulosic fibers and superabsorbent particles; wherein the inner core layer comprises from about 125 gsm to about 400 gsm of cellulosic fibers; wherein the wearer-facing surface of the absorbent article comprises a flexural bond channel region having a dry MD flexural resistance of less than about 0.04 N / mm as measured according to the Flexural Bond Channel MD Flexural Resistance Method and a Flexural Resistance of about 0.05 g / cm 3 To about 0.3g / cm 3 channel density.

[0371] Paragraph R. A disposable absorbent article according to Paragraph Q, wherein the flex bond channel region has a channel depth of at least 1 mm.

[0372] Paragraph S. The disposable absorbent article of any of Paragraphs Q to R, wherein the flex bond channel region has a channel width of about 1.0 mm to about 3.0 mm.

[0373] Paragraph T. The disposable absorbent article of any of Paragraphs Q to S, wherein the flex bond channel region has a minimum channel length of about 50 mm.

[0374] Paragraph U. A disposable absorbent article according to any of paragraphs Q to T, wherein the absorbent article has a thickness, and wherein the flex bond channel region has an average channel depth of about 20% to about 80% of the thickness of the absorbent article.

[0375] Paragraph V. The disposable absorbent article of any of Paragraphs Q to U, wherein the outwardly facing surface comprises one or more flex bond depressions.

[0376] Paragraph W. A disposable absorbent article comprising: a top sheet; a back sheet; an absorbent core structure disposed between the top sheet and the back sheet, wherein the absorbent core structure comprises an upper nonwoven layer comprising polymer fibers and an inner core layer comprising about 125 gsm to about 400 gsm cellulose fibers; wherein the inner core layer has a wearer-facing surface and an outward-facing surface, and the upper nonwoven layer is in direct contact with the wearer-facing surface of the inner core layer; and a flexural bond channel region comprising one or more flexural bond embossments having an embossment length of about 1.0 mm to about 4.0 mm; wherein the flexural bond channel region has a channel depth of at least 1.0 mm and a channel width of about 1.0 mm to about 3.0 mm; wherein the flexural bond channel region has a dry MD flexural resistance of less than about 0.04 N / mm, as measured according to the Flexural Bond Channel MD Flexural Resistance Method.

[0377] Paragraph Y. The disposable absorbent article of Paragraph W, wherein the absorbent core structure further comprises a lower nonwoven layer comprising polymer fibers and in direct contact with the outwardly facing surface of the inner core layer.

[0378] Paragraph X. The disposable absorbent article of Paragraphs W to Y, wherein the one or more flex bond embossments have an area ranging from about 22% to about 65% of the area of ​​the flex bond channel region.

[0379] Paragraph Z. A disposable absorbent article according to Paragraphs W to X, wherein the one or more flex bond channel regions have a g / cm 3 To about 0.3g / cm 3 channel density.

[0380] Paragraph A1. The disposable absorbent article of Paragraphs A to Z, wherein the inner core layer is contained within the nonwoven layer by substantially sealing at least left and right regions of the upper nonwoven layer and the lower nonwoven.

[0381] The dimensions and values ​​disclosed herein should not be understood as being strictly limited to the exact numerical values ​​cited. Instead, unless otherwise indicated, each such dimension is intended to represent the stated value and a functionally equivalent range around that value. For example, a dimension disclosed as "40 mm" is intended to mean "about 40 mm".

[0382] Unless expressly excluded or otherwise limited, each document cited herein, including any cross-referenced or related patent or application, is incorporated herein by reference in its entirety. Citation of any document is not an admission that it is prior art to any of the present invention disclosed or claimed herein, or that it, by itself or in combination with any one or more references, proposes, suggests, or discloses any such invention. In addition, to the extent that any meaning or definition of a term in this invention conflicts with any meaning or definition of the same term in a document incorporated by reference, the meaning or definition assigned to that term in this invention shall govern.

[0383] Although specific embodiments of the present invention have been illustrated and described, it will be apparent to those skilled in the art that various other changes and modifications may be made without departing from the spirit and scope of the present invention. Therefore, it is intended that all such changes and modifications within the scope of the present invention be covered in the appended claims.

Claims

1. A disposable absorbent article, comprising: A front end region, a rear end region, and an intermediate region disposed between the front end region and the rear end region; Top sheet; negative film; An absorbent core structure, the absorbent core structure being disposed between the top sheet and the back sheet, wherein the absorbent core structure comprises: a. an upper nonwoven layer, the upper nonwoven layer comprising polymer fibers; b. a lower nonwoven layer comprising polymer fibers; and c. an inner core layer disposed between the upper nonwoven layer and the lower nonwoven layer, wherein the inner core layer comprises cellulose fibers and superabsorbent particles; and a flex bond channel region formed in at least the intermediate region; wherein the flex bond channel region has a dry channel depth of at least 1.0 mm and a channel width of 1.0 mm to 3.0 mm; and wherein the flex bond channel region has a CD flex index of 1.1 to 3.0, and a dry MD flex resistance of less than 0.04 N / mm, as measured according to the Flex Bond Channel MD Flex Method.

2. The disposable absorbent article of claim 1, wherein the dry MD flexural resistance is from 0.005 N / mm to 0.035 N / mm as measured according to the Flex Bond Channel MD Flexural Resistance method.

3. The disposable absorbent article of claim 1 or 2, wherein the flex bond channel region has a minimum channel length of at least 50 mm.

4. A disposable absorbent article according to any one of the preceding claims, wherein the flex bond channel area includes one or more flex bond embossments and one or more flex bond landing areas arranged between each of the flex bond embossments.

5. The disposable absorbent article of claim 4, wherein each of the flex bond land areas can have a thickness between 50% and 70% of the thickness of the absorbent article.

6. The disposable absorbent article of claim 4 wherein the flex bond embossment has an embossment area and the flex bond channel region has a channel area, wherein the embossment area is from 22% to 65% of the channel area.

7. The disposable absorbent article of claim 4, wherein the flex bond embossments have an embossment length of 1.0 mm to 4.0 mm.

8. The disposable absorbent article of claim 4, wherein each of the flex bond land areas has a length of 0.5 mm to 4 mm.

9. The disposable absorbent article according to any one of the preceding claims, wherein the absorbent article comprises an inner flex bond channel area and an outer flex bond channel area.

10. The disposable absorbent article according to any one of the preceding claims, wherein the absorbent article has an average density between 0.045 g / cm3 and 0.15 g / cm3.

11. The disposable absorbent article of any one of the preceding claims, wherein the flex bond channel regions have a thermal conductivity of 0.05 g / cm 3 Up to 0.3g / cm 3 channel density.

12. The disposable absorbent article according to any one of the preceding claims, wherein the upper nonwoven has a basis weight of 35 gsm to 85 gsm.

13. The disposable absorbent article according to any one of the preceding claims, wherein the lower nonwoven has a basis weight of from 10 gsm to 40 gsm.

14. The disposable absorbent article according to any one of the preceding claims, wherein the inner core layer comprises 50% to 85% by weight of the inner core layer of cellulose fibers and 15% to 50% by weight of the inner core layer of superabsorbent particles.

15. The disposable absorbent article according to any one of the preceding claims, wherein the absorbent article has a CD Dry Bending Stiffness between 10 N.mm2 and 30 N.mm2 as measured according to the Wet and Dry CD and MD 3-Point Bend Method, and a Fifth Cycle Wet Recovery % between 29% and 40% as measured according to the Wet and Dry Gather Compression Method.

Citation Information

Patent Citations

  • Apertured macroscopically expanded three-dimensional polymeric web exhibiting breatheability and resistance to fluid transmission and use thereof in an absorbent article

    EP0203821A2

  • Breathable backsheet design for disposable absorbent articles

    EP0710471A1

  • Breathable dual layer backsheet design for disposable absorbent articles

    EP0710472A1

  • Absorbent articles having fluid contact angle gradients between the topsheet and absorbent core

    EP0793952A1

  • Fluid management layer for an absorbent article

    US12138146B2